Freshwater biodiversity in a rapidly changing Arctic: An expert horizon scan of key research questions - Joseph M. Culp; Michael Power; Kirsten S. Christoffersen; Willem Goedkoop; Kimmo K. Kahilainen; Milla Rautio; Fernando Chaguaceda; Marie-Pier Hébert; Sanne M. Moedt; Dermot Antoniades; Simon Belle; Daniel Bolnick; et al. (Ambio, 2026)
Arctic freshwater biodiversity is rapidly changing due to climate warming, resource extraction, infrastructure development, and landscape transformation. To improve understanding, predict future responses, and inform policy formulation, research needs must be clearly identified. Using a horizon scan survey, Arctic freshwater experts from government, international agencies, and Indigenous Peoples identified 77 biodiversity research questions with 17 highlighted as most important for near term assessment. These questions span nine thematic categories: biodiversity and taxonomic challenges, hydrological change, productivity and food webs, ecosystem connectivity, methods, monitoring and assessment, permafrost change, winter ecology, anthropogenic development, and Indigenous Knowledge. Climate change emerged as the major driver among all categories and research questions. A key priority identified was the urgent need for long-term, harmonized monitoring programs among Arctic countries. Multiple knowledge gaps detected suggest that circumpolar research collaborations are required to tackle these issues.

Extreme environmental conditions are associated with poor recruitment of an estuarine sportfish - Manuel E. Coffill-Rivera; Zhilong Liu; John C. Lehrter; Brian Dzwonkowski; Jason M. Cope; Julie M. Gross; John Mareska; Sean P. Powers (Fisheries Research, 2026)

Petrography and pore-scale assessment of CO2 mineral trapping potential of sedimentary strata beneath the lower mainland British Columbia, Canada - Paula Ramirez-Lopez; Shahin E. Dashtgard; Marc Enter; Matthew Power; Dirk Kirste; Maziyar Nazemi; Francyne Bochi do Amarante (International Journal of Greenhouse Gas Control, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Corticospinal excitability is higher during synchronous vs asynchronous arm cycling - Jirho A. Ogolo; Evan J. Lockyer; Farahmand Fattaneh; Kate Rait; Kevin E. Power (European Journal of Applied Physiology, 2026)

A critical review of potential modifiers of air pollutant associations with dementia and related outcomes - JeongWon Han; Yina Li; Sangji Lee; Katie M. Lynch; Erin E. Bennett; Qi Ying; Eun Sug Park; Richard L. Smith; James D. Stewart; Eric A. Whitsel; Melinda C. Power; Xiaohui Xu (NeuroToxicology, 2026)

Millennial-scale fire and climate dynamics in the world's largest tropical wetland show emerging fire threat to flooded ecosystems - Bronwen S. Whitney; Danilo M. Neves; Nicholas J.D. Loughlin; Carlos D'Apolito; Carla Coblinski Tavares; Emma P. Hocking; Francis E. Mayle; Mitchell J. Power; Aguinaldo Silva; Mario L. Assine (Global and Planetary Change, 2026)

Nutrient Transfer Dynamics of Anadromous Alewives (Alosa pseudoharengus) in Freshwater Spawning and Nursery Habitats - Robert E. Vincent; John M. Logan; John J. Sheppard; Michael Power; Stephen T. Hurley; Kevin Bennett (Estuaries and Coasts, 2026)
River herring (alewife, Alosa pseudoharengus and blueback herring, A . aestivalis ) can act as vectors of nutrient transfer between marine and freshwater environments. Adult river herring can transfer marine-derived nutrients to freshwater ecosystems during spawning migrations through excretions and direct consumption of adults, eggs, and early phase juveniles by freshwater scavengers and predators. Adults and juveniles can transfer nutrients derived during freshwater residency back to the marine environment following emigration and the same excretion and consumption mechanisms. Potential nutrient transfers were assessed by applying carbon, nitrogen, and sulfur stable isotope analyses to a collection of juvenile and adult alewives, baseline food web components, and freshwater fish predators in three ponds in southeastern Massachusetts USA. Out-migrating adult alewife tissue stable isotope values were lower for both carbon and sulfur but higher for nitrogen than in-migrating conspecifics reflecting incorporation of freshwater-derived nutrients. Most juvenile alewife stable isotope values were at steady state with freshwater food webs at the time of sampling reflecting additional export of freshwater-derived nutrients with their eventual emigration to the marine environment. Stable isotope-based detection of marine-derived nutrients in freshwater predators was limited to catadromous elvers ( Anguilla rostrata ), anadromous white perch ( Morone americana ), and semi-anadromous yellow perch ( Perca flavescens ) with no marine-derived nutrients detected in resident freshwater fish predators. However, juvenile alewives were observed in stomachs of smallmouth ( Micropterus dolomieu ) and largemouth bass ( M . nigricans ). Results further inform current alewife ecosystem-level interactions with the marine and freshwater environments that they occupy during different life history phases for the many coastal watersheds in New England.

Retrogressive Thaw Slumps Produce a Changing Disturbance Regime for Arctic Stream Invertebrates - Maria Dolan; Jordan Musetta‐Lambert; Krista S. Chin; Steven V. Kokelj; Suzanne E. Tank; Jennifer Lento; Michael Power; Joseph M. Culp (Global Change Biology, 2026)
For many Arctic rivers and streams, climate‐driven intensification of permafrost thaw slumping is a major source of disturbance to aquatic habitats. Thaw slumps are dynamic landforms that severely increase total suspended solids (TSS) and nutrients in downstream reaches and can persist over decades. Effects may differ in magnitude as slumps cycle through periods of higher and lower activity, with expansion of retrogressive slumps increasing over time. Increases in TSS are known to cause reduced invertebrate abundance and diversity in impacted watersheds; however, it remains unclear if water quality and critical aquatic biodiversity have recovered after prolonged exposure to slumps. Here, we examined decadal‐scale effects of slumps and environmental change on benthic macroinvertebrates (BMI) by comparing environmental and BMI data collected between 2010–2014 and a recent sampling campaign from 2021. High TSS and nutrient concentrations observed during 2010–2014 persisted in slump‐impacted sites in 2021, with no significant change in TSS and total nutrient concentrations after the 10‐year exposure period. TSS continued to act as a nonspecific stressor on BMI, as abundance remained significantly lower in impacted streams compared to reference streams. Although total abundance within reference and impacted sites did not differ significantly between sampling periods, abundance and richness of disturbance tolerant taxa was greater in 2021 as compared to 2010–2014 across all sites, with differences linked to lower precipitation in 2021. These community compositional changes were reflected in increased Shannon‐Weiner diversity between sampling campaigns. Overall, the number of thaw slumps upstream was an important driver of both BMI abundance and diversity across sampling periods and will likely continue to be an important determinant of benthic macroinvertebrate communities as the number and size of thaw slumps continues to increase across the circumpolar Arctic.

Regional ecosystem responses to environmental drivers in cold‐water lakes evaluated using stable isotopes of salmonid fishes - Matthew R. D. Cobain; Per‐Arne Amundsen; Åge Brabrand; Pär Byström; Jan G. Davidsen; Karl Ø. Gjelland; Jennifer E. Hansen; Ingeborg P. Helland; Trygve Hesthagen; Stein I. Johnsen; Roger I. Jones; Kimmo K. Kahilainen; et al. (Limnology and Oceanography, 2026)
Diverse environmental drivers influence food web energy and nutrient flows, a key ecosystem function, yet their relative importance remains poorly known. We compiled thousands of bulk stable isotope measurements (carbon and nitrogen) of brown trout ( Salmo trutta , n = 2854) and Arctic charr ( Salvelinus alpinus , n = 3062) from 120 cold‐water lakes across northern Europe, spanning 0.02 to 1090 km 2 in size, to quantify the relative importance of nine potential drivers of energy and nutrient flows. Fish community type and individual body size matched the well‐described ecologies of the two species: charr shifted from littoral to pelagic sources with interspecific competition, and trout opportunistically increased their trophic position with piscivorous prey availability and increasing body size. The anthropogenic impacts of water‐level regulation and catchment modification were mirrored in the two species, resulting in decreased δ 13 C values, implying increased relative pelagic production in regulated lakes, and increased δ 15 N values, possibly due to increasing cross‐boundary nutrient flows. Lake size and climatic drivers (summer precipitation and winter temperature) elicited strong species‐specific changes in isotope values, suggesting that predator‐driven ecological responses can dominate over ecosystem‐wide changes in energy and nutrient flows within lake food webs. No isotopic trends were observed with catchment productivity or shoreline complexity at the regional scale, contrasting with insights from local scale studies. This spatial mismatch suggests that environmental drivers of ecosystem processes playing out at the regional scale cannot necessarily be extrapolated from localized studies, despite correlated random lake effects capturing unexplained local baseline shifts in isotopes.

A statistical representation of oil spill fate in the Salish Sea (Part 1) - Rachael D. Mueller; Susan E. Allen; Stephanie Chang; Haibo Niu; Douglas J. Latornell; Shihan Li; Ryah Bagshaw; Ashutosh Bhudia; Vicky Do; Krista Forysinski; Ben Moore-Maley; Cameron Power (Marine Pollution Bulletin, 2026)

Transcription of immune genes in ranched southern bluefin tuna show correlations to Cardicola spp. (Digenea: Aporocotylidae) infection - Maree Widdicombe; Sarah Eastwood; Bronwyn E. Campbell; Cecilia Power; Barbara F. Nowak; Paul A. Ramsland; Nathan J. Bott (Aquaculture, 2026)

A statistical representation of oil spill fate in the Salish Sea (Part 2) - Rachael D. Mueller; Susan E. Allen; Stephanie Chang; Haibo Niu; Douglas J. Latornell; Shihan Li; Ryah Bagshaw; Ashutosh Bhudia; Vicky Do; Krista Forysinski; Ben Moore-Maley; Cameron Power (Marine Pollution Bulletin, 2025)

Association of midlife air pollution and road proximity exposure with 29-year cognitive decline - Melinda C. Power; Ziwei Song; Annie Chen; Katie M. Lynch; Naa Adoley Parker-Allotey; Erin E. Bennett; Xiaohui Xu; Eric A. Whitsel; Richard L. Smith; James D. Stewart; Eun Sug Park; Qi Ying; et al. (NeuroToxicology, 2025)

Pre- and post-move exposure to air pollution and neighborhood socioeconomic status - Chelsea Liu; Erin E. Bennett; Katie M. Lynch; Xiaohui Xu; Eun Sug Park; Qi Ying; Richard L. Smith; James D. Stewart; Eric A. Whitsel; Joel D. Kaufman; Emma K. Stapp; Melinda C. Power (Science of The Total Environment, 2025)

Development of a fipronil insecticide response spectrum model for juvenile Chinook salmon (Oncorhynchus tshawytscha) - Kara E. Huff Hartz; Katie J. Knaub; Louise Cominassi; Giovanni S. Molinari; Shane Power; Mia Arkles; S.D.M. Chinthaka; Andrea Chandler; Md. Habibullah-Al-Mamun; Gregory Whitledge; Amelie Segarra; Richard E. Connon; et al. (Environmental Pollution, 2025)

Using a critical body residue approach to assess the acute toxicity of a pesticide mixture to juvenile Chinook salmon (Oncorhynchus tshawytscha) - Kara E. Huff Hartz; Mia Arkles; Katie J. Knaub; Shane D. Power; Giovanni S. Molinari; S.D.M. Chinthaka; Gregory Whitledge; Amelie Segarra; Richard E. Connon; Shawn Acuña; Michael J. Lydy (Environmental Pollution, 2025)

Fishery-independent camera surveys provide novel observations of white sharks (Carcharodon carcharias) off coastal Alabama - J. Marcus Drymon; Amanda E. Jargowsky; Theodore S. Switzer; Crystal L. Hightower; Sean P. Powers (Frontiers in Marine Science, 2025)
Determining the distributions of marine animals is a challenge, particularly for highly migratory species like sharks. In the United States, several shark populations are beginning to recover following exploitation, including the white shark ( Carcharodon carcharias ). Recently, reports of white sharks have increased in the northern Gulf of Mexico (hereafter Gulf), but determining whether these reports represent actual changes in distribution is difficult. Therefore, we examined two long-term fishery-independent camera datasets to assess whether the recent increase in reports of white sharks reflects changes in distribution or typical (albeit rare) events. Long-term fishery-independent stereo-baited remote underwater video (sBRUV) and remotely operated vehicle (ROV) datasets were examined. From 2010 – 2024, 8368 sBRUV and 2199 ROV surveys were conducted. From 2010 – 2023, no white sharks were seen on either camera gear, but two white sharks were observed on ROV videos in 2024. The first was a female estimated at 239 cm total length and the second was a male estimated at 191 cm total length. These observations lend support to the notion that recent reports of white sharks in the northern Gulf may indicate early evidence of range-edge expansion rather than increases in telemetry efforts or citizen observations. Studies like this one highlight the value of long-term, randomized, fishery-independent camera surveys for documenting changes in distribution for rare species.

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Nitrogen fixation in Pampinifervens, a new species-rich genus of Aquificaceae that inhabits a wide pH range in terrestrial hot springs - Marike Palmer; Nancy O. Nou; Lara A. Turello; Carolyn E. Power; John C. Ong; Jonathan K. Covington; Dengxun Lai; Xavier Mayali; Anna-Louise Reysenbach; Yan-Ling Qi; Jeremy A. Dodsworth; Jian-Yu Jiao; et al. (Systematic and Applied Microbiology, 2025)

Balancing practicality and aspiration: A comparative analysis of sustainable holistic planning system toolkit designs - Anne E. Mosher; Stephen Bird; Santosh K. Mahapatra; Susan E. Powers; Joseph D. Skufca; Erik C. Backus (Landscape and Urban Planning, 2025)

Supplemental Feeding as a Driver of Population Expansion and Morphological Change in Anna's Hummingbirds - Nicolas M. Alexandre; Faye G. Romero; Simon G. English; Eliza Grames; Felipe Garzón‐Agudelo; Kevin Epperly; Timothy Barnes; Donald R. Powers; Audrey E. Smith; Zoë Migicovsky; Laura Stein; Saron Akalu; et al. (Global Change Biology, 2025)
Bird beaks are highly adaptable, with the potential to undergo rapid morphological shifts in response to environmental change such as climatic variation or food availability. Anna's Hummingbirds ( Calypte anna ) have undergone dramatic population range expansions over the last 160 years into novel climatic regimes, where supplemental feeders and introduced plant species are frequented. We used museum specimens to measure and characterize the shape of Anna's Hummingbird bills, hypothesizing that the introduction of novel food sources and the colonization of colder climates were associated with distinct dimensions of beak morphology. We estimated feeder and Eucalyptus availability using data from archived newspaper databases and found that these two abundances are linked to population increases in Anna's Hummingbirds, while feeders were associated with changes to beak morphology. We found that bill size and shape changed with feeder use, exhibiting a more tapered and longer bill and a distinct maxillary constriction. In males, dorsal bill shape increased in pointedness, which may have provided an advantage with increased agonistic encounters at feeders. In contrast, bill size decreased in association with lower temperatures at higher latitudes. Our data document rapid morphological changes in the Anna's Hummingbird's bill induced by human‐caused environmental changes over the last century.

Statistical properties of multi-year droughts in climate models and observations with corresponding theoretical estimates - Scott B. Power; Zoe E. Gillett (Climate Dynamics, 2025)
Multi-year droughts (MYDs) can have major impacts on ecosystems, agriculture, water resources, economies, people and societies. Here, we examine statistical properties of MYDs consisting of uninterrupted sequences of years in which annual precipitation falls below a given threshold. We examine statistics including the proportion of years that are part of droughts of duration $$\ge n$$ ≥ n years, the proportion of droughts that have duration $$\ge n$$ ≥ n years, and both the duration and the number of droughts with duration $$\ge n$$ ≥ n years, in thirty-eight 200-year-long simulations of CMIP6 coupled global climate models under pre-industrial control conditions. We also derive formulae that approximate the average value of these and other statistics using simple stochastic models. The theoretical values obtained agree reasonably well with their Multi-Model Mean (MMM) climate model counterparts over the globe. Regional contrasts in the value of the statistics for MYDs consisting of uninterrupted sequences of years with below-average precipitation can be largely explained by spatial variations in the percentile of the mean. Corresponding formulae that account for non-zero temporal autocorrelation tend to agree somewhat more closely with the MMM values. MYD statistics are estimated using observational data and compared with theoretical and climate model estimates. The formulae incorporating non-zero autocorrelation provide a better estimate of the observational values than do MMM values or formulae derived assuming zero autocorrelation.

Chemical Composition of Secretions from Facial Glands of Captive Hoary Bat (Lasiurus cinereus) in Virginia - Kristina R. Stefaniak; Lark Kellogg; Matthew T. Close; Karen E. Powers (Journal of Chemical Ecology, 2025)
Our study represents the first known report of hoary bat ( Lasiurus cinereus ) facial gland histology and chemical characterization of facial gland secretions. While in captivity from October 2023 to February 2024, facial secretions of a male hoary bat were observed and collected. Gas chromatography-mass spectrometry (GC-MS) analysis of a methanol extraction of November 2023 samples identified 23 compounds after comparing retention times, mass spectra, and Kovats retention index. These compounds consisted of alkanes, alcohols, ketones, terpenoids, monoacylglycerols, and androgens. Of interest was the identification of five androstane derivatives, testosterone metabolites, that have not been seen previously in mammal secretions and indicate possible mating readiness. The chemical analyses from November swabs and histological examination of facial skin in February suggest that this male was actively secreting mate-signaling compounds throughout late fall and winter months. Anecdotal mating records on wintering grounds combined with this bat’s warm captive environment likely allowed for this extended mating readiness for his many months at the wildlife center.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Remote sensing for species distribution models: An illustration from a sentinel taxon of the world's driest ecosystem - Khum B. Thapa‐Magar; Eric R. Sokol; Michael N. Gooseff; Mark R. Salvatore; John E. Barrett; Joseph S. Levy; Paul Knightly; Sarah N. Power (Ecology, 2025)
In situ observed data are commonly used as species occurrence response variables in species distribution models. However, the use of remotely observed data from high‐resolution multispectral remote‐sensing images as a source of presence/absence data for species distribution models remains under‐developed. Here, we describe an ensemble species distribution model of black microbial mats ( Nostoc spp.) using presence/absence points derived from the unmixing of 4‐m resolution WorldView‐2 and WorldView‐3 images in the Lake Fryxell basin region of Taylor Valley, Antarctica. Environmental and topographical characteristics such as soil moisture, snow, elevation, slope, and aspect were used as predictor variables in our models. We demonstrate that we can build and run ensemble species distribution models using both dependent and independent variables derived from remote‐sensing data to generate spatially explicit habitat suitability maps. Snow and soil moisture were found to be the most important variables accounting for about 80% of the variation in the distribution of black mats throughout the Fryxell basin. This study highlights the potential contribution of high‐resolution remote‐sensing to species distribution modeling and informs new studies incorporating remotely derived species occurrences in species distribution models, especially in remote areas where access to in situ data is often limited.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Road salt chloride exposure in urban streambeds and links to groundwater – surface water interactions and salt sources - Grant Hodgins; Clare E. Robinson; Christopher Power; James W. Roy (Science of The Total Environment, 2024)

Past fire dynamics in sub-Saharan Africa during the last 25,000 years: Climate change and increasing human impacts - Laurent Bremond; Julie C. Aleman; Charly Favier; Olivier Blarquez; Daniele Colombaroli; Simon E. Connor; Carlos E. Cordova; Colin Courtney-Mustaphi; Abraham N. Dabengwa; Graciela Gil-Romera; William D. Gosling; Tamryn Hamilton; et al. (Quaternary International, 2024)

Association of midlife air pollution exposures and residential road proximity with incident dementia: The Atherosclerosis Risk in Communities (ARIC) study - Ziwei Song; Katie Lynch; Naa Adoley Parker-Allotey; Erin E. Bennett; Xiaohui Xu; Eric A. Whitsel; Richard Smith; James D. Stewart; Eun Sug Park; Qi Ying; Melinda C. Power (Environmental Research, 2024)

Spatially varying impacts of pacific and southern ocean climate modes on tidal residuals in New South Wales, Australia - Cristina N.A. Viola; Danielle C. Verdon-Kidd; Hannah E. Power (Estuarine, Coastal and Shelf Science, 2024)

A comparison of PM2.5 exposure estimates from different estimation methods and their associations with cognitive testing and brain MRI outcomes - Melinda C. Power; Katie M. Lynch; Erin E. Bennett; Qi Ying; Eun Sug Park; Xiaohui Xu; Richard L. Smith; James D. Stewart; Jeff D. Yanosky; Duanping Liao; Aaron van Donkelaar; Joel D. Kaufman; et al. (Environmental Research, 2024)

Correction: Progress in the analysis of English Channel loliginid squid diets using DNA-metabarcoding techniques - A. Larivain; C. Zatylny-Gaudin; E. Gonzalez; G. J. Pierce; A. M. Power; J. P. Robin (Marine Biology, 2024)

Depredation: An old conflict with the sea - James Marcus Drymon; Amanda E. Jargowsky; Evan G. Prasky; Edward V. Camp; Ashley Oliphant; Sean P. Powers; Steven B. Scyphers (Fish and Fisheries, 2024)
Depredation (the partial or complete removal of a hooked species by a non‐target species) is a human–wildlife conflict as old as humans and the sea. In some ways, depredation is no different today than it was a century ago. But in many ways, this conflict has become more complicated. Following three decades of successful management, some US shark populations have begun to rebuild. However, many anglers attribute perceived increases in shark depredation to management measures, claiming they have led to ‘overpopulation’ of sharks and/or learned behaviour by sharks. We investigated whether these factors could explain the reported increases in depredation. Based on fishery‐independent surveys, neither shark population increases nor learned behaviour by sharks is evident. However, increases in angler effort provide an alternative explanation that is not often considered. While far from a smoking gun, at least four themes emerge from this thought exercise. First, it is important to understand historical predator baselines. Second, it is important to acknowledge lifting baselines, that is, instances where previously depleted populations are recovering. Third, it is important to remember that there are many instances when stakeholder observations were initially misaligned with traditional scientific observations but were ultimately recognized as pivotal for filling data gaps. Finally, and perhaps most important, is the acknowledgement that perceived conflict is as potent as real conflict. Arguably, it may not matter if depredation has increased or decreased; the overwhelming perception from stakeholders is an increase in depredation, and this is the perceived (or real) conflict that must be addressed.

From field station to forecast: managing data at the Alaska Volcano Observatory - Michelle L. Coombs; Cheryl E. Cameron; Hannah R. Dietterich; Eleanor S. Boyce; Aaron G. Wech; Ronni Grapenthin; Kristi L. Wallace; Tom Parker; Taryn Lopez; Scott Crass; David Fee; Matthew M. Haney; et al. (Bulletin of Volcanology, 2024)

Characterising continental shelf waves and their drivers for the southeast coast of Australia - Cristina N.A. Viola; Danielle C. Verdon-Kidd; Hannah E. Power (Ocean & Coastal Management, 2024)

Progress in the analysis of English Channel loliginid squid diets using DNA-metabarcoding techniques - A. Larivain; C. Zatylny-Gaudin; E. Gonzalez; G. J. Pierce; A. M. Power; J. P. Robin (Marine Biology, 2024)

Local environment shapes milk microbiomes while evolutionary history constrains milk macronutrients in captive cercopithecine primates - Sally L. Bornbusch; Hannah E. Shinnerl; Lindsey Gentry; Mia M. Keady; Virginia Glick; Carly R. Muletz‐Wolz; Michael L. Power (Environmental Microbiology, 2024)
Milk is a complex biochemical fluid that includes macronutrients and microbiota, which, together, are known to facilitate infant growth, mediate the colonization of infant microbiomes, and promote immune development. Examining factors that shape milk microbiomes and milk‐nutrient interplay across host taxa is critical to resolving the evolution of the milk environment. Using a comparative approach across four cercopithecine primate species housed at three facilities under similar management conditions, we test for the respective influences of the local environment (housing facility) and host species on milk (a) macronutrients (fat, sugar, and protein), (b) microbiomes (16S rRNA), and (c) predicted microbial functions. We found that milk macronutrients were structured according to host species, while milk microbiomes and predicted function were strongly shaped by the local environment and, to a lesser extent, host species. The milk microbiomes of rhesus macaques ( Macaca mulatta ) at two different facilities more closely resembled those of heterospecific facility‐mates compared to conspecifics at a different facility. We found similar, facility‐driven patterns of microbial functions linked to physiology and immune modulation, suggesting that milk microbiomes may influence infant health and development. These results provide novel insight into the complexity of milk and its potential impact on infants across species and environments.

Habitat-dependent metabolic costs for a wild cold-water fish - Benjamin L. Hlina; Daniel M. Glassman; Elodie J. I. Lédée; Liane B. Nowell; Julie E. Claussen; David P. Philipp; J. Ellen Marsden; Michael Power; Steven J. Cooke (Aquatic Sciences, 2024)

Characterization of subsurface pathways contributing to freshwater salinization of urban streams using electrical and electromagnetic imaging techniques - Grant Hodgins; Clare E. Robinson; James W. Roy; Christopher Power (Science of The Total Environment, 2023)

Sea level rise and the increasing frequency of inundation in Australia’s most exposed estuary - David J. Hanslow; Martin G. Fitzhenry; Michael G. Hughes; Michael A. Kinsela; Hannah E. Power (Regional Environmental Change, 2023)
The large tidal lake systems along the Southeast Australian coast are amongst the most vulnerable estuaries in Australia to the effects of sea level rise. In these lakes, reduced tide ranges compared with the ocean, in combination with modest flood extremes, have allowed development to occur in close vertical proximity to the current mean sea level. In this study, we examine water levels within Lake Macquarie, Australia’s most exposed estuary to sea level rise. We analyse water level data from the entrance channel and the lake to investigate recent changes to the frequency and duration of inundation or flooding of low-lying streets and examine the potential impacts of future rises in sea level. Our analysis shows that the numbers of days each year when water levels exceed those of low-lying streets, while subject to some variability, have increased significantly over recent decades. The increasing frequency of inundation is attributed to both mean sea level rise and an increase in tide range over the period of available data, which is thought to be associated with scour processes related to ongoing morphological adjustment to entrance training works undertaken over a century ago. Comparison of the projected behaviour of lake and open coast water levels under sea level rise shows the lake has significantly greater sensitivity to sea level rise. Projected inundation frequency for a given amount of sea level rise within the lake is double that of open coast sites, exposing infrastructure in the estuary to increasing risk of damage.

A randomized placebo-controlled trial of nicotinamide riboside in older adults with mild cognitive impairment - Miranda E. Orr; Eithan Kotkowski; Paulino Ramirez; Darcy Bair-Kelps; Qianqian Liu; Charles Brenner; Mark S. Schmidt; Peter T. Fox; Anis Larbi; Crystal Tan; Glenn Wong; Jonathan Gelfond; et al. (GeroScience, 2023)

Spring temperature predicts upstream migration timing of invasive Sacramento pikeminnow within its introduced range - Philip B. Georgakakos; David N. Dralle; Mary E. Power (Environmental Biology of Fishes, 2023)
Rapid climate change and invasive species introductions threaten ecological communities across the globe. Freshwaters are particularly vulnerable and impacted, especially when these stresses coincide. We document the migration of an invasive piscine predator, the Sacramento pikeminnow ( Ptychocheilus grandis ), within its introduced range, the South Fork Eel River, California, USA. Snorkel surveys and temperature monitoring in 2015–2019 showed that pikeminnow migrate upstream during spring and early summer, with earlier migration in warmer years. We developed a statistical temperature model to forecast the timing and extent of upstream migration by pikeminnow under varying combinations of discharge and air temperature. Modeled river temperature increased with air temperature and downstream and decreased with discharge. In years with low discharge and high air temperature, we predict pikeminnow will move upstream earlier, increasing spatial and temporal overlap in their summer range with native fishes. Managing conditions that reduce pikeminnow co-occurrence with native fishes (i.e., decreasing river temperature) could increase amount and duration of predator-free habitat for native fishes. We predict invasive pikeminnow will have larger impacts on invaded riverine communities with global warming and increasing drought severity. Knowledge of life history and phenology, for pikeminnow and other organisms, can guide effective management as conditions change and help to limit adverse impacts of introduced organisms on native species.

An improved method for computing tidal datums - Karen Palmer; Christopher S. Watson; John R. Hunter; Ben S. Hague; Hannah E. Power (Coastal Engineering, 2023)

The Western Lake Erie culture collection: A promising resource for evaluating the physiological and genetic diversity of Microcystis and its associated microbiome - Colleen E. Yancey; E. Anders Kiledal; Subba Rao Chaganti; Vincent J. Denef; Reagan M. Errera; Jacob T. Evans; Lauren N. Hart; Dragan Isailovic; William S. James; Jenan J. Kharbush; Jeffrey A. Kimbrel; Wei Li; et al. (Harmful Algae, 2023)

High-resolution entry and exit surface dosimetry in a 1.5 T MR-linac - E. Patterson; P. Stokes; D. Cutajar; A. Rosenfeld; J. Baines; P. Metcalfe; M. Powers (Physical and Engineering Sciences in Medicine, 2023)
The magnetic field of a transverse MR-linac alters electron trajectories as the photon beam transits through materials, causing lower doses at flat entry surfaces and increased doses at flat beam-exiting surfaces. This study investigated the response of a MOSFET detector, known as the MO Skin ™, for high-resolution surface and near-surface percentage depth dose measurements on an Elekta Unity. Simulations with Geant4 and the Monaco treatment planning system (TPS), and EBT-3 film measurements, were also performed for comparison. Measured MO Skin ™ entry surface doses, relative to D max , were (9.9 ± 0.2)%, (10.1 ± 0.3)%, (11.3 ± 0.6)%, (12.9 ± 1.0)%, and (13.4 ± 1.0)% for 1 × 1 cm 2 , 3 × 3 cm 2 , 5 × 5 cm 2 , 10 × 10 cm 2 , and 22 × 22 cm 2 fields, respectively. For the investigated fields, the maximum percent differences of Geant4, TPS, and film doses extrapolated and interpolated to a depth suitable for skin dose assessment at the beam entry, relative to MO Skin ™ measurements at an equivalent depth were 1.0%, 2.8%, and 14.3%, respectively, and at a WED of 199.67 mm at the beam exit, 3.2%, 3.7% and 5.7%, respectively. The largest measured increase in exit dose, due to the electron return effect, was 15.4% for the 10 × 10 cm 2 field size using the MO Skin ™ and 17.9% for the 22 × 22 cm 2 field size, using Geant4 calculations. The results presented in the study validate the suitability of the MO Skin ™ detector for transverse MR-linac surface dosimetry.

Drivers of the microbial metabolic quotient across global grasslands - A. C. Risch; S. Zimmermann; M. Schütz; E. T. Borer; A. A. D. Broadbent; M. C. Caldeira; K. F. Davies; N. Eisenhauer; A. Eskelinen; P. A. Fay; F. Hagedorn; J. M. H. Knops; et al. (Global Ecology and Biogeography, 2023)
Aim The microbial metabolic quotient (MMQ; mg CO 2 ‐C/mg MBC/h), defined as the amount of microbial CO 2 respired (MR; mg CO 2 ‐C/kg soil/h) per unit of microbial biomass C (MBC; mg C/kg soil), is a key parameter for understanding the microbial regulation of the carbon (C) cycle, including soil C sequestration. Here, we experimentally tested hypotheses about the individual and interactive effects of multiple nutrient addition (nitrogen + phosphorus + potassium + micronutrients) and herbivore exclusion on MR, MBC and MMQ across 23 sites (five continents). Our sites encompassed a wide range of edaphoclimatic conditions; thus, we assessed which edaphoclimatic variables affected MMQ the most and how they interacted with our treatments. Location Australia, Asia, Europe, North/South America. Time period 2015–2016. Major taxa Soil microbes. Methods Soils were collected from plots with established experimental treatments. MR was assessed in a 5‐week laboratory incubation without glucose addition, MBC via substrate‐induced respiration. MMQ was calculated as MR/MBC and corrected for soil temperatures (MMQsoil). Using linear mixed effects models (LMMs) and structural equation models (SEMs), we analysed how edaphoclimatic characteristics and treatments interactively affected MMQsoil. Results MMQsoil was higher in locations with higher mean annual temperature, lower water holding capacity and lower soil organic C concentration, but did not respond to our treatments across sites as neither MR nor MBC changed. We attributed this relative homeostasis to our treatments to the modulating influence of edaphoclimatic variables. For example, herbivore exclusion, regardless of fertilization, led to greater MMQsoil only at sites with lower soil organic C ( Main conclusions Our results pinpoint the main variables related to MMQsoil across grasslands and emphasize the importance of the local edaphoclimatic conditions in controlling the response of the C cycle to anthropogenic stressors. By testing hypotheses about MMQsoil across global edaphoclimatic gradients, this work also helps to align the conflicting results of prior studies.

Aquatic environmental DNA: A review of the macro-organismal biomonitoring revolution - Miwa Takahashi; Mattia Saccò; Joshua H. Kestel; Georgia Nester; Matthew A. Campbell; Mieke van der Heyde; Matthew J. Heydenrych; David J. Juszkiewicz; Paul Nevill; Kathryn L. Dawkins; Cindy Bessey; Kristen Fernandes; et al. (Science of The Total Environment, 2023)

The relationship between single muscle fibre and voluntary rate of force development in young and old males - Benjamin E. Dalton; Nicole Mazara; Mathew I. B. Debenham; Derek P. Zwambag; Alex M. Noonan; Erin Weersink; Stephen H. M. Brown; Geoffrey A. Power (European Journal of Applied Physiology, 2023)

More than an anthropogenic phenomenon: Antimicrobial resistance in ungulates from natural and agricultural environments - Lee J. Pinnell; Grace Kuiper; Kate L. Huebner; Enrique Doster; Jennifer K. Parker; Najla Alekozai; Jenny G. Powers; Rick L. Wallen; Keith E. Belk; Paul S. Morley (Science of The Total Environment, 2023)

Green-up and brown-down: Modelling grassland foliage phenology responses to soil moisture availability - Jinyan Yang; Belinda E. Medlyn; Craig V.M. Barton; Amber C. Churchill; Martin G. De Kauwe; Mingkai Jiang; Arjunan Krishnananthaselvan; David T. Tissue; Elise Pendall; Sally A. Power (Agricultural and Forest Meteorology, 2023)

Hyperspectral imaging predicts yield and nitrogen content in grass–legume polycultures - K. R. Ball; H. Liu; C. Brien; B. Berger; S. A. Power; E. Pendall (Precision Agriculture, 2022)

Age, growth and diet of crevalle jack ( Caranx hippos ) in the Gulf of Mexico - Amanda E. Jefferson; Matthew B. Jargowsky; Genevieve M. Ivec; Pearce T. Cooper; Jessica L. Carroll; Carissa L. Gervasi; Jennifer S. Rehage; John F. Mareska; Sean P. Powers; J. Marcus Drymon (Fisheries Management and Ecology, 2022)
The goals of this study were to generate baseline population dynamics parameters for Gulf of Mexico crevalle jack Caranx hippos and examine the foraging habits of Mississippi and Alabama crevalle jack. Specimens were collected from Mississippi, Alabama and Florida, and age was estimated from sagittal otoliths. Stomachs from some specimens were retained for dietary analyses. Age classes spanned 0–20 years. Overall growth was best represented by the logistic growth model, whereas sex‐specific growth was best represented by a version of the von Bertalanffy growth function that allowed L ∞ to vary by sex while holding k and t 0 constant between sexes. Fishes were more important to crevalle jack diet than invertebrates, and diet varied among locations and years. These findings will address fundamental knowledge gaps to inform age‐based stock assessments for crevalle jack and ecosystem approaches to fisheries management in the Gulf of Mexico.

Interhemispheric inhibition is different during arm cycling than a position- and intensity-matched tonic contraction - Chris T. Compton; Evan J. Lockyer; Ryan J. Benson; Kevin E. Power (Experimental Brain Research, 2022)

Summer ecosystem structure in mountain lakes linked to interannual variability of lake ice, snowpack, and landscape attributes - Stephen M. Powers; Steven C. Fradkin; William Baccus; Carmen Archambault; John R. Boetsch; Matthew R. Brousil; Rebecca Lofgren; Ashley Rawhouser; Stephanie E. Hampton (Limnology and Oceanography, 2022)
Mountain lakes experience interannual variability in spring snowpack and ice cover that can lead to differences in physical, chemical, and biological properties in the succeeding summer. Lake studies that capture extreme years of snow and ice would be useful to understand and anticipate effects of climate change, but such data are rare for remote mountain lakes. Monitoring of lakes in Olympic, North Cascades, and Mount Rainier National Parks from 2007 to 2018 allowed us to examine limnological differences along interannual and elevation‐driven climate gradients that included unusually high (2011–2012) and 100‐yr record low (2015) snowpack years. Years with lower spring snowpack had earlier ice‐out. Across lakes, our analysis suggested an average of 0.075°C lake warming per day of lost ice duration (0.525°C per week), giving rise to other ecosystem changes linked to temperature such as lower dissolved oxygen, higher total dissolved N, higher chlorophyll, and higher abundance of cladoceran zooplankton. Conversely, in years with higher snowpack and a shorter ice‐free season, lakes were colder and clearer (1 m deeper Secchi depth for every 1 m May snow water equivalent), with more dilute ions as well as lower algal biomass and zooplankton abundance. These results add to evidence that changes in snowpack or ice‐out dates alter mountain lake ecology through multiple processes associated with hydrology, terrestrial‐aquatic connection, water temperature, productivity, ion composition, and plankton communities.

Transmission of Klebsiella strains and plasmids within and between grey‐headed flying fox colonies - Ben Vezina; Louise M. Judd; Fiona K. McDougall; Wayne S. J. Boardman; Michelle L. Power; Jane Hawkey; Sylvain Brisse; Jonathan M. Monk; Kathryn E. Holt; Kelly L. Wyres (Environmental Microbiology, 2022)
Summary The grey‐headed flying fox ( Pteropus poliocephalus ) is an endemic Australian fruit bat, known to carry zoonotic pathogens. We recently showed they harbour bacterial pathogen Klebsiella pneumoniae and closely related species in the K . pneumoniae species complex ( Kp SC); however, the dynamics of Kp SC transmission and gene flow within flying fox colonies are poorly understood. High‐resolution genome comparisons of 39 Kp SC isolates from grey‐headed flying foxes identified five putative strain transmission clusters (four intra‐ and one inter‐colony). The instance of inter‐colony strain transmission of K . africana was found between two flying fox populations within flying distance, indicating either direct or indirect transmission through a common food/water source. All 11 plasmids identified within the Kp SC isolates showed 73% coverage (mean) and ≥95% identity to human‐associated Kp SC plasmids, indicating gene flow between human clinical and grey‐headed flying fox isolates. Along with strain transmission, inter‐species horizontal plasmid transmission between K . pneumoniae and Klebsiella africana was also identified within a flying fox colony. Finally, genome‐scale metabolic models were generated to predict and compare substrate usage to previously published Kp SC models, from human and environmental sources. These models indicated no distinction on the basis of metabolic capabilities. Instead, metabolic capabilities were consistent with population structure and ST/lineage.

Strategies to acquire and use phosphorus in phosphorus-impoverished and fire-prone environments - Hans Lambers; Patrícia de Britto Costa; Gregory R. Cawthray; Matthew D. Denton; Patrick M. Finnegan; Patrick E. Hayes; Rafael S. Oliveira; Simon C. Power; Kosala Ranathunge; Qi Shen; Xiao Wang; Hongtao Zhong (Plant and Soil, 2022)
Background Unveiling the diversity of plant strategies to acquire and use phosphorus (P) is crucial to understand factors promoting their coexistence in hyperdiverse P-impoverished communities within fire-prone landscapes such as in cerrado (South America), fynbos (South Africa) and kwongan (Australia). Scope We explore the diversity of P-acquisition strategies, highlighting one that has received little attention: acquisition of P following fires that temporarily enrich soil with P. This strategy is expressed by fire ephemerals as well as fast-resprouting perennial shrubs. A plant’s leaf manganese concentration ([Mn]) provides significant clues on P-acquisition strategies. High leaf [Mn] indicates carboxylate-releasing P-acquisition strategies, but other exudates may play the same role as carboxylates in P acquisition. Intermediate leaf [Mn] suggests facilitation of P acquisition by P-mobilising neighbours, through release of carboxylates or functionally similar compounds. Very low leaf [Mn] indicates that carboxylates play no immediate role in P acquisition. Release of phosphatases also represents a P-mining strategy, mobilising organic P. Some species may express multiple strategies, depending on time since germination or since fire, or on position in the landscape. In severely P-impoverished landscapes, photosynthetic P-use efficiency converges among species. Efficient species exhibit rapid rates of photosynthesis at low leaf P concentrations. A high P-remobilisation efficiency from senescing organs is another way to use P efficiently, as is extended longevity of plant organs. Conclusions Many P-acquisition strategies coexist in P-impoverished landscapes, but P-use strategies tend to converge. Common strategies of which we know little are those expressed by ephemeral or perennial species that are the first to respond after a fire. We surmise that carboxylate-releasing P-mobilising strategies are far more widespread than envisaged so far, and likely expressed by species that accumulate metals, exemplified by Mn, metalloids, such as selenium, fluorine, in the form of fluoroacetate, or silicon. Some carboxylate-releasing strategies are likely important to consider when restoring sites in biodiverse regions as well as in cropping systems on P-impoverished or strongly P-sorbing soils, because some species may only be able to establish themselves next to neighbours that mobilise P.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Endurance-exercise training adaptations in spinal motoneurones: potential functional relevance to locomotor output and assessment in humans - Kevin E. Power; Evan J. Lockyer; Alberto Botter; Taian Vieira; Duane C. Button (European Journal of Applied Physiology, 2022)

The Ocean's labile DOC supply chain - Mary Ann Moran; Frank X. Ferrer‐González; He Fu; Brent Nowinski; Malin Olofsson; McKenzie A. Powers; Jeremy E. Schreier; William F. Schroer; Christa B. Smith; Mario Uchimiya (Limnology and Oceanography, 2022)
Microbes of the surface ocean release, consume, and exchange labile metabolites at time scales of minutes to days. The details of this important step in the global carbon cycle remain poorly resolved, largely due to the methodological challenges of studying a diverse pool of metabolites that are produced and consumed nearly simultaneously. In this perspective, a new compilation of published data builds on previous studies to obtain an updated estimate of the fraction of marine net primary production that passes through the labile dissolved organic carbon (DOC) pool. In agreement with previous studies, our data mining and modeling approaches hypothesize that about half of ocean net primary production is processed through the labile DOC pool. The fractional contributions from three major sources are estimated at 0.4 for living phytoplankton, 0.4 for dead and dying phytoplankton, and 0.2 for heterotrophic microbes and mesoplankton.

Challenges and opportunities of the fourth revolution: a brief insight into the future of food - James Chapman; Aoife Power; Michael E. Netzel; Yasmina Sultanbawa; Heather E. Smyth; Vic Khanh Truong; Daniel Cozzolino (Critical Reviews in Food Science and Nutrition, 2022)

Post-traumatic Osteoarthritis in Rabbits Following Traumatic Injury and Surgical Reconstruction of the Knee - Feng Wei; Madeleine J. F. Powers; Gerardo E. Narez; Loic M. Dejardin; Tammy Haut Donahue; Roger C. Haut (Annals of Biomedical Engineering, 2022)

Perspectives on the environmental implications of sustainable hydro-power: comparing countries, problems and approaches - K. Alfredsen; I. P. Helland; E. G. Martins; M. Power (Hydrobiologia, 2022)

A synoptic history of the development, production and environmental oversight of hydropower in Brazil, Canada, and Norway - K. Alfredsen; P.-A. Amundsen; L. Hahn; P. M. Harrison; I. P. Helland; E. G. Martins; W. M. Twardek; M. Power (Hydrobiologia, 2022)

Microcoleus (Cyanobacteria) form watershed‐wide populations without strong gradients in population structure - Keith Bouma‐Gregson; Alexander Crits‐Christoph; Mathew R. Olm; Mary E. Power; Jillian F. Banfield (Molecular Ecology, 2022)
The relative importance of separation by distance and by environment to population genetic diversity can be conveniently tested in river networks, where these two drivers are often independently distributed over space. To evaluate the importance of dispersal and environmental conditions in shaping microbial population structures, we performed genome‐resolved metagenomic analyses of benthic Microcoleus ‐dominated cyanobacterial mats collected in the Eel and Russian River networks (California, USA). The 64 Microcoleus genomes were clustered into three species that shared >96.5% average nucleotide identity (ANI). Most mats were dominated by one strain, but minor alleles within mats were often shared, even over large spatial distances (>300 km). Within the most common Microcoleus species, the ANI between the dominant strains within mats decreased with increasing spatial separation. However, over shorter spatial distances (tens of kilometres), mats from different subwatersheds had lower ANI than mats from the same subwatershed, suggesting that at shorter spatial distances environmental differences between subwatersheds in factors like canopy cover, conductivity, and mean annual temperature decreases ANI. Since mats in smaller creeks had similar levels of nucleotide diversity ( π ) as mats in larger downstream subwatersheds, within‐mat genetic diversity does not appear to depend on the downstream accumulation of upstream‐derived strains. The four‐gamete test and sequence length bias suggest recombination occurs between almost all strains within each species, even between populations separated by large distances or living in different habitats. Overall, our results show that, despite some isolation by distance and environmental conditions, sufficient gene‐flow occurs among cyanobacterial strains to prevent either driver from producing distinctive population structures across the watershed.

The genetic and ecophysiological diversity of Microcystis - Gregory J. Dick; Melissa B. Duhaime; Jacob T. Evans; Reagan M. Errera; Casey M. Godwin; Jenan J. Kharbush; Helena S. Nitschky; McKenzie A. Powers; Henry A. Vanderploeg; Kathryn C. Schmidt; Derek J. Smith; Colleen E. Yancey; et al. (Environmental Microbiology, 2021)
Summary Microcystis is a cyanobacterium that forms toxic blooms in freshwater ecosystems around the world. Biological variation among taxa within the genus is apparent through genetic and phenotypic differences between strains and via the spatial and temporal distribution of strains in the environment, and this fine‐scale diversity exerts strong influence over bloom toxicity. Yet we do not know how varying traits of Microcystis strains govern their environmental distribution, the tradeoffs and links between these traits, or how they are encoded at the genomic level. Here we synthesize current knowledge on the importance of diversity within Microcystis and on the genes and traits that likely underpin ecological differentiation of taxa. We briefly review spatial and environmental patterns of Microcystis diversity in the field and genetic evidence for cohesive groups within Microcystis . We then compile data on strain‐level diversity regarding growth responses to environmental conditions and explore evidence for variation of community interactions across Microcystis strains. Potential links and tradeoffs between traits are identified and discussed. The resulting picture, while incomplete, highlights key knowledge gaps that need to be filled to enable new models for predicting strain‐level dynamics, which influence the development, toxicity and cosmopolitan nature of Microcystis blooms.

Counting Carbon: Quantifying Biomass in the McMurdo Dry Valleys through Orbital & Field Observations - Mark R. Salvatore; John E. Barrett; Schuyler R. Borges; Sarah N. Power; Lee F. Stanish; Eric R. Sokol; Michael N. Gooseff (International Journal of Remote Sensing, 2021)

Relationship Between Time-Weighted Head Impact Exposure on Directional Changes in Diffusion Imaging in Youth Football Players - Suraj K. Puvvada; Elizabeth M. Davenport; James M. Holcomb; Logan E. Miller; Christopher T. Whitlow; Alexander K. Powers; Joseph A. Maldjian; Joel D. Stitzel; Jillian E. Urban (Annals of Biomedical Engineering, 2021)

Integrating Ecological Stoichiometry to Understand Nutrient Limitation and Potential for Competition in Mixed Pasture Assemblages - K. R. Ball; S. J. Woodin; S. A. Power; C. Brien; B. Berger; P. Smith; E. Pendall (Journal of Soil Science and Plant Nutrition, 2021)

Chronic resistance training: is it time to rethink the time course of neural contributions to strength gain? - G. E. P. Pearcey; S. Alizedah; K. E. Power; D. C. Button (European Journal of Applied Physiology, 2021)

Estimating and Applying Fish and Invertebrate Density and Production Enhancement from Seagrass, Salt Marsh Edge, and Oyster Reef Nursery Habitats in the Gulf of Mexico - Philine S. E. zu Ermgassen; Bryan DeAngelis; Jonathan R. Gair; Sophus zu Ermgassen; Ronald Baker; Andre Daniels; Timothy C. MacDonald; Kara Meckley; Sean Powers; Marta Ribera; Lawrence P. Rozas; Jonathan H. Grabowski (Estuaries and Coasts, 2021)
Seagrasses, oyster reefs, and salt marshes are critical coastal habitats that support high densities of juvenile fish and invertebrates. Yet which species are enhanced through these nursery habitats, and to what degree, remains largely unquantified. Densities of young-of-year fish and invertebrates in seagrasses, oyster reefs, and salt marsh edges as well as in paired adjacent unstructured habitats of the northern Gulf of Mexico were compiled. Species consistently found at higher densities in the structured habitats were identified, and species-specific growth and mortality models were applied to derive production enhancement estimates arising from this enhanced density. Enhancement levels for fish and invertebrate production were similar for seagrass (1370 [SD 317] g m –2 y –1 for 25 enhanced species) and salt marsh edge habitats (1222 [SD 190] g m –2 y –1 , 25 spp.), whereas oyster reefs produced ~650 [SD 114] g m –2 y –1 (20 spp). This difference was partly due to lower densities of juvenile blue crab ( Callinectes sapidus ) on oyster reefs, although only oyster reefs enhanced commercially valuable stone crabs ( Menippe spp.). The production estimates were applied to Galveston Bay, Texas, and Pensacola Bay, Florida, for species known to recruit consistently in those embayments. These case studies illustrated variability in production enhancement by coastal habitats within the northern Gulf of Mexico. Quantitative estimates of production enhancement within specific embayments can be used to quantify the role of essential fish habitat, inform management decisions, and communicate the value of habitat protection and restoration.

Deciphering the role of cartilage protein 1 in human dermal fibroblasts: a transcriptomic approach - Sophia Letsiou; Manuel Manchado; Mariela Zografaki; Sofia Marka; Liliana Anjos; Dimitrios Skliros; Juan F. Martínez-Blanch; E. Flemetakis; Deborah M. Power (Functional & Integrative Genomics, 2021)

Research Priorities for Coastal Geoscience and Engineering: A Collaborative Exercise in Priority Setting From Australia - Hannah E. Power; Andrew W. M. Pomeroy; Michael A. Kinsela; Thomas P. Murray (Frontiers in Marine Science, 2021)
We present the result of a collaborative priority setting exercise to identify emerging issues and priorities in coastal geoscience and engineering (CGE). We use a ranking process to quantify the criticality of each priority from the perspective of Australian CGE researchers and practitioners. 74 activities were identified across seven categories: Data Collection and Collation, Coastal Dynamics and Processes, Modelling, Engineering Solutions, Coastal Hazards and Climate Change, Communication and Collaboration, and Infrastructure, Innovation, and Funding. We found consistent and unanimous support for the vast majority of priorities identified by the CGE community, with 91% of priorities being allocated a score of ≥ 3 out of 5 (i.e., above average levels of support) by ≥ 75% of respondents. Data Collection and Collation priorities received the highest average score, significantly higher than four of the other six categories, with Coastal Hazards and Climate Change the second ranked category and Engineering Solutions the lowest scoring category. Of the 74 priorities identified, 11 received unified and strong support across the CGE community and indicate a critical need for: additional coastal data collection including topographic and bathymetric, hydrodynamic, oceanographic, and remotely sensed data; improved data compilation and access; improved understanding of extreme events and the quantification of future impacts of climate change on nearshore dynamics and coastal development; enhanced quantification of shoreline change and coastal inundation processes; and, additional funding to support CGE research and applications to mitigate and manage coastal hazards. The outcomes of this priority setting exercise can be applied to guide policy development and decision-making in Australia and jurisdictions elsewhere. Further, the research and application needs identified here will contribute to addressing key practical challenges identified at a national level. CGE research plays a critical role in identifying and enabling social, environmental, and economic benefits through the proactive management of coastal hazard impacts and informed planning to mitigate the potential impacts of growing coastal risk, particularly in a changing climate. The prevalence and commonalities of the challenges faced by coastal communities globally due to increasing pressures from coastal hazards in a changing climate suggest that our findings will be applicable to other settings.

Brain Strain: Computational Model-Based Metrics for Head Impact Exposure and Injury Correlation - Logan E. Miller; Jillian E. Urban; Elizabeth M. Davenport; Alexander K. Powers; Christopher T. Whitlow; Joseph A. Maldjian; Joel D. Stitzel (Annals of Biomedical Engineering, 2021)

Estimating microbial mat biomass in the McMurdo Dry Valleys, Antarctica using satellite imagery and ground surveys - Sarah N. Power; Mark R. Salvatore; Eric R. Sokol; Lee F. Stanish; J. E. Barrett (Polar Biology, 2020)

Combined use of radiocarbon and stable carbon isotopes for the source mixing model in a stream food web - Naoto F. Ishikawa; Jacques C. Finlay; Hiromi Uno; Nanako O. Ogawa; Naohiko Ohkouchi; Ichiro Tayasu; Mary E. Power (Limnology and Oceanography, 2020)
Radiocarbon natural abundance (Δ 14 C) has emerged as a useful dietary tracer in freshwater ecology for the past decade, yet its applicability for separating aquatic and terrestrial resources has not been examined quantitatively. Here, we report Δ 14 C values of stream invertebrates in different functional feeding groups collected from the upper South Fork Eel River watershed, northern California. We found that algae‐grazing insect larvae show low Δ 14 C values (−43.1 ± 21.8‰, mean ± standard deviation, N = 6), reflecting the signal of dissolved inorganic carbon weathered from ancient inorganic carbon or respiration of old organic carbon. In contrast, the Δ 14 C values of leaf‐shredding insect larvae (21.7 ± 31.9‰, N = 5) were close to those of contemporary atmospheric CO 2 except at the SF Eel River where algal production was highest. The Δ 14 C values of predators (−6.1 ± 35.7‰, N = 14) were intermediate between those of grazers and shredders. In a Bayesian mixing model, Δ 14 C provided a more ecologically realistic estimate for terrestrial vs. aquatic source contributions to invertebrates with lower uncertainty (i.e., narrower credible interval) than did the stable carbon isotopes (δ 13 C). These results demonstrate that Δ 14 C can be used, in combination with δ 13 C, to more precisely estimate organic matter sources to stream animals.

Ecometrics and the paleoecological implications of Pleistocene faunas from the western coastal plains of the Cape Floristic Region, South Africa - J. Tyler Faith; David R. Braun; Benjamin Davies; Larisa R. G. DeSantis; Matthew J. Douglass; Irene Esteban; Vincent Hare; Naomi E. Levin; Julie Luyt; Robyn Pickering; Mitchell J. Power; Judith Sealy; et al. (Journal of Quaternary Science, 2020)
The Pleistocene ungulate communities from the western coastal plains of South Africa's Cape Floristic Region (CFR) are diverse and dominated by grazers, in contrast to the region's Holocene and historical faunas, which are relatively species‐poor and dominated by small‐bodied browsers and mixed feeders. An expansion of grassy habitats is clearly implied by the Pleistocene faunas, but the presence of ruminant grazers that cannot survive the summer dry season typical of the region today suggests other important paleoecological changes. Here we use dental ecometrics to explore the paleoecological implications of the region's Pleistocene faunas. We show that the dental traits (hypsodonty and occlusal topography) of the ungulates that occurred historically in the CFR track annual and summer aridity, and we use these relationships to reconstruct past aridity. Our results indicate that the Pleistocene faunas signal paleoenvironments that were on average less arid than today, including during the summer, consistent with other lines of evidence that suggest a higher water table and expansion of well‐watered habitats. Greater water availability can be explained by lower temperature and reduced evapotranspiration during cooler phases of the Pleistocene, probably coupled with enhanced groundwater recharge due to increased winter precipitation.

Predicting adult lifespan and lifetime reproductive success from early-life reproductive events - Matthew J. Powers; Ryan J. Weaver; Kyle B. Heine; Geoffrey E. Hill (Marine Biology, 2020)

Microbial processing of plant remains is co‐limited by multiple nutrients in global grasslands - Raúl Ochoa‐Hueso; Elizabeth T. Borer; Eric W. Seabloom; Sarah E. Hobbie; Anita C. Risch; Scott L. Collins; Juan Alberti; Héctor A. Bahamonde; Cynthia S. Brown; Maria C. Caldeira; Pedro Daleo; Chris R. Dickman; et al. (Global Change Biology, 2020)
Microbial processing of aggregate‐unprotected organic matter inputs is key for soil fertility, long‐term ecosystem carbon and nutrient sequestration and sustainable agriculture. We investigated the effects of adding multiple nutrients (nitrogen, phosphorus and potassium plus nine essential macro‐ and micro‐nutrients) on decomposition and biochemical transformation of standard plant materials buried in 21 grasslands from four continents. Addition of multiple nutrients weakly but consistently increased decomposition and biochemical transformation of plant remains during the peak‐season, concurrent with changes in microbial exoenzymatic activity. Higher mean annual precipitation and lower mean annual temperature were the main climatic drivers of higher decomposition rates, while biochemical transformation of plant remains was negatively related to temperature of the wettest quarter. Nutrients enhanced decomposition most at cool, high rainfall sites, indicating that in a warmer and drier future fertilized grassland soils will have an even more limited potential for microbial processing of plant remains.

Tsunami Modelling with Static and Dynamic Tides in Drowned River Valleys with Morphological Constrictions - Kaya M. Wilson; Hannah E. Power (Pure and Applied Geophysics, 2020)

Evaluation of Australian Tsunami Warning Thresholds Using Inundation Modelling - Diana J. M. Greenslade; Burak Uslu; Stewart C. R. Allen; Claire L. Kain; Kaya M. Wilson; Hannah E. Power (Pure and Applied Geophysics, 2020)

Effect of Shallow Slip Amplification Uncertainty on Probabilistic Tsunami Hazard Analysis in Subduction Zones: Use of Long-Term Balanced Stochastic Slip Models - A. Scala; S. Lorito; F. Romano; S. Murphy; J. Selva; R. Basili; A. Babeyko; A. Herrero; A. Hoechner; F. Løvholt; F. E. Maesano; P. Perfetti; et al. (Pure and Applied Geophysics, 2020)

Defining Sex-Specific Habitat Suitability for a Northern Gulf of Mexico Shark Assemblage - J. M. Drymon; S. Dedman; J. T. Froeschke; E. A. Seubert; A. E. Jefferson; A. M. Kroetz; J. F. Mareska; S. P. Powers (Frontiers in Marine Science, 2020)

The Presence of a High Peak Feature Within Low-Average Shear Stimuli Induces Quiescence in Venous Endothelial Cells - M. Franzoni; D. T. O’Connor; L. Marcar; D. Power; M. A. Moloney; E. G. Kavanagh; R. L. Leask; J. Nolan; P. A. Kiely; M. T. Walsh (Annals of Biomedical Engineering, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Transcutaneous electrical nerve stimulation improves fatigue performance of the treated and contralateral knee extensors - D. G. Behm; E. M. Colwell; G. M. J. Power; H. Ahmadi; A. S. M. Behm; A. Bishop; C. Murph; J. Pike; B. McAssey; K. Fraser; S. Kearley; M. Ryan (European Journal of Applied Physiology, 2019)

Assessing Nearshore Nekton Abundance, Substrate, and Environmental Conditions in the Northern Gulf of Mexico: Are There Differences Among Three Adjacent Coastal Areas and Have There Been Changes over Three Decades (1986–2015)? - Martin T. O’Connell; Mark S. Peterson; Sean P. Powers; Ann M. Uzee-O’Connell; E. John Anderson; J. Read Hendon (Estuaries and Coasts, 2019)

DIBI, a novel 3-hydroxypyridin-4-one chelator iron-binding polymer, inhibits breast cancer cell growth and functions as a chemosensitizer by promoting S-phase DNA damage - Anna L. Greenshields; Melanie R. Power Coombs; Wasundara Fernando; Bruce E. Holbein; David W. Hoskin (BioMetals, 2019)

3D seismic-derived bathymetry: a quantitative comparison with multibeam data - H. E. Power; S. L. Clarke (Geo-Marine Letters, 2019)

Arctic shrub colonization lagged peak postglacial warmth: Molecular evidence in lake sediment from Arctic Canada - Sarah E. Crump; Gifford H. Miller; Matthew Power; Julio Sepúlveda; Nadia Dildar; Megan Coghlan; Michael Bunce (Global Change Biology, 2019)
Arctic shrubification is an observable consequence of climate change, already resulting in ecological shifts and global‐scale climate feedbacks including changes in land surface albedo and enhanced evapotranspiration. However, the rate at which shrubs can colonize previously glaciated terrain in a warming world is largely unknown. Reconstructions of past vegetation dynamics in conjunction with climate records can provide critical insights into shrubification rates and controls on plant migration, but paleoenvironmental reconstructions based on pollen may be biased by the influx of exotic pollen to tundra settings. Here, we reconstruct past plant communities using sedimentary ancient DNA ( sed aDNA), which has a more local source area than pollen. We additionally reconstruct past temperature variability using bacterial cell membrane lipids (branched glycerol dialkyl glycerol tetraethers) and an aquatic productivity indicator (biogenic silica) to evaluate the relative timing of postglacial ecological and climate changes at a lake on southern Baffin Island, Arctic Canada. The sed aDNA record tightly constrains the colonization of dwarf birch ( Betula , a thermophilous shrub) to 5.9 ± 0.1 ka, ~3 ka after local deglaciation as determined by cosmogenic 10 Be moraine dating and >2 ka later than Betula pollen is recorded in nearby lake sediment. We then assess the paleovegetation history within the context of summer temperature and find that paleotemperatures were highest prior to 6.3 ka, followed by cooling in the centuries preceding Betula establishment. Together, these molecular proxies reveal that Betula colonization lagged peak summer temperatures, suggesting that inefficient dispersal, rather than climate, may have limited Arctic shrub migration in this region. In addition, these data suggest that pollen‐based climate reconstructions from high latitudes, which rely heavily on the presence and abundance of pollen from thermophilous taxa like Betula , can be compromised by both exotic pollen fluxes and vegetation migration lags.

Short-interval intracortical inhibition of the biceps brachii in chronic-resistance versus non-resistance-trained individuals - Behzad Lahouti; Evan J. Lockyer; Shawn Wiseman; Kevin E. Power; Duane C. Button (Experimental Brain Research, 2019)

Tiger sharks eat songbirds: reply - J. M. Drymon; K. Feldheim; A. M. V. Fournier; E. A. Seubert; A. E. Jefferson; A. M. Kroetz; S. P. Powers (Ecology, 2019)

Short-interval intracortical inhibition to the biceps brachii is present during arm cycling but is not different than a position- and intensity-matched tonic contraction - L. R. Alcock; A. J. Spence; E. J. Lockyer; D. C. Button; Kevin E. Power (Experimental Brain Research, 2019)

Tiger sharks eat songbirds: scavenging a windfall of nutrients from the sky - J. M. Drymon; K. Feldheim; A. M. V. Fournier; E. A. Seubert; A. E. Jefferson; A. M. Kroetz; S. P. Powers (Ecology, 2019)

Whole Genome Sequence Analysis of Burkholderia contaminans FFH2055 Strain Reveals the Presence of Putative β-Lactamases - José J. Degrossi; Cindy Merino; Adela M. Isasmendi; Lorena M. Ibarra; Chelsea Collins; Nicolás E. Bo; Mariana Papalia; Jennifer S. Fernandez; Claudia M. Hernandez; Krisztina M. Papp-Wallace; Robert A. Bonomo; Miryam S. Vazquez; et al. (Current Microbiology, 2019)

Diverse effects of the common hippopotamus on plant communities and soil chemistry - Douglas J. McCauley; Stuart I. Graham; Todd E. Dawson; Mary E. Power; Mordecai Ogada; Wanja D. Nyingi; John M. Githaiga; Judith Nyunja; Lacey F. Hughey; Justin S. Brashares (Oecologia, 2018)

Recent ecological change in ancient lakes - Stephanie E. Hampton; Suzanne McGowan; Ted Ozersky; Salvatore G. P. Virdis; Tuong Thuy Vu; Trisha L. Spanbauer; Benjamin M. Kraemer; George Swann; Anson W. Mackay; Stephen M. Powers; Michael F. Meyer; Stephanie G. Labou; et al. (Limnology and Oceanography, 2018)
Ancient lakes are among the best archivists of past environmental change, having experienced more than one full glacial cycle, a wide range of climatic conditions, tectonic events, and long association with human settlements. These lakes not only record long histories of environmental variation and human activity in their sediments, but also harbor very high levels of biodiversity and endemism. Yet, ancient lakes are faced with a familiar suite of anthropogenic threats, which may degrade the unusual properties that make them especially valuable to science and society. In all ancient lakes for which data exist, significant warming of surface waters has occurred, with a broad range of consequences. Eutrophication threatens both native species assemblages and regional economies reliant on clean surface water, fisheries, and tourism. Where sewage contributes nutrients and heavy metals, one can anticipate the occurrence of less understood emerging contaminants, such as pharmaceuticals, personal care products, and microplastics that negatively affect lake biota and water quality. Human populations continue to increase in most of the ancient lakes’ watersheds, which will exacerbate these concerns. Further, human alterations of hydrology, including those produced through climate change, have altered lake levels. Co‐occurring with these impacts have been intentional and unintentional species introductions, altering biodiversity. Given that the distinctive character of each ancient lake is strongly linked to age, there may be few options to remediate losses of species or other ecosystem damage associated with modern ecological change, heightening the imperative for understanding these systems.

Effects of competition and herbivory over woody seedling growth in a temperate woodland trump the effects of elevated CO2 - L. Collins; M. M. Boer; V. Resco de Dios; S. A. Power; E. R. Bendall; S. Hasegawa; R. Ochoa Hueso; J. Piñeiro Nevado; R. A. Bradstock (Oecologia, 2018)

Experimentally altered rainfall regimes and host root traits affect grassland arbuscular mycorrhizal fungal communities - Coline Deveautour; Suzanne Donn; Sally A. Power; Alison E. Bennett; Jeff R. Powell (Molecular Ecology, 2018)
Future climate scenarios predict changes in rainfall regimes. These changes are expected to affect plants via effects on the expression of root traits associated with water and nutrient uptake. Associated microorganisms may also respond to these new precipitation regimes, either directly in response to changes in the soil environment or indirectly in response to altered root trait expression. We characterized arbuscular mycorrhizal (AM) fungal communities in an Australian grassland exposed to experimentally altered rainfall regimes. We used Illumina sequencing to assess the responses of AM fungal communities associated with four plant species sampled in different watering treatments and evaluated the extent to which shifts were associated with changes in root traits. We observed that altered rainfall regimes affected the composition but not the richness of the AM fungal communities, and we found distinctive communities in the increased rainfall treatment. We found no evidence of altered rainfall regime effects via changes in host physiology because none of the studied traits were affected by changes in rainfall. However, specific root length was observed to correlate with AM fungal richness, while concentrations of phosphorus and calcium in root tissue and the proportion of root length allocated to fine roots were correlated to community composition. Our study provides evidence that climate change and its effects on rainfall may influence AM fungal community assembly, as do plant traits related to plant nutrition and water uptake. We did not find evidence that host responses to altered rainfall drive AM fungal community assembly in this grassland ecosystem.

A comparison of the trophic ecology of Beaufort Sea Gadidae using fatty acids and stable isotopes - J. D. Brewster; C. Giraldo; E. S. Choy; S. A. MacPhee; C. Hoover; B. Lynn; D. G. McNicholl; A. Majewski; B. Rosenberg; M. Power; J. D. Reist; L. L. Loseto (Polar Biology, 2018)

Daily temperature experience and selection by adfluvial bull trout (Salvelinus confluentus) - L. F. G. Gutowsky; P. M. Harrison; E. G. Martins; A. Leake; D. A. Patterson; D. Z. Zhu; M. Power; S. J. Cooke (Environmental Biology of Fishes, 2017)

Rhizosphere-driven increase in nitrogen and phosphorus availability under elevated atmospheric CO2 in a mature Eucalyptus woodland - Raúl Ochoa-Hueso; John Hughes; Manuel Delgado-Baquerizo; John E. Drake; Mark G. Tjoelker; Juan Piñeiro; Sally A. Power (Plant and Soil, 2017)

DIMBOA levels in hexaploid Brazilian wheat are not associated with antibiosis against the cereal aphids Rhopalosiphum padi and Sitobion avenae - Jorge F. Pereira; André L. F. Sarria; Stephen J. Powers; Gudbjorg I. Aradottir; John C. Caulfield; Janet Martin; Lesley E. Smart; John A. Pickett; Michael A. Birkett; Paulo R. V. S. Pereira (Theoretical and Experimental Plant Physiology, 2017)

Effects of water level regulation in alpine hydropower reservoirs: an ecosystem perspective with a special emphasis on fish - Philipp E. Hirsch; Antti P. Eloranta; Per-Arne Amundsen; Åge Brabrand; Julie Charmasson; Ingeborg P. Helland; Michael Power; Javier Sánchez-Hernández; Odd Terje Sandlund; Julian F. Sauterleute; Sigrid Skoglund; Ola Ugedal; et al. (Hydrobiologia, 2017)

Testing the Use of Static Chamber Boxes to Monitor Greenhouse Gas Emissions from Wood Chip Storage Heaps - Carly Whittaker; Nicola E. Yates; Stephen J. Powers; Neil Donovan; Tom Misselbrook; Ian Shield (BioEnergy Research, 2017)

Individual isotopic specializations predict subsequent inter‐individual variation in movement in a freshwater fish - P. M. Harrison; L. F. G. Gutowsky; E. G. Martins; T. D. Ward; D. A. Patterson; S. J. Cooke; M. Power (Ecology, 2017)
Despite many similarities and intuitive links between individual dietary specialization and behavioral inter‐individual variation, these phenomena have been studied in isolation, and empirical data confirming relationships between these intraspecific variance sources are lacking. Here we use stable isotope analysis and acoustic telemetry to test the hypothesis that individual specialization in trophic (δ 15 N) and littoral/pelagic prey reliance (δ 13 C) covary with inter‐individual variation in movement in a group of 34 free‐swimming burbot ( Lota lota ). By performing stable isotope analysis on tissues with differing isotopic turnover rates (anal fin and dorsal muscle), in 24 lethally sampled burbot, we demonstrate that individual specialization in trophic niche (δ 15 N) and littoral/pelagic prey reliance (δ 13 C) occurred within the population. By performing stable isotope analysis on anal fins of a group of telemetry tagged burbot, we were able to show that interactions between trophic niche and littoral/pelagic prey reliance, explained a significant proportion of the subsequent between‐individual variance in mean movement rates. These findings demonstrate an empirical connection between behavioral inter‐individual variation and dietary specialization, thus providing a substantial expansion of our understanding of the wider ecological consequences of these interesting phenomena.

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

The role of Salvelinus in contemporary studies of evolution, trophic ecology and anthropogenic change - Rune Knudsen; Anders Klemetsen; Sergey Alekseyev; Colin E. Adams; Michael Power (Hydrobiologia, 2016)

Attentional function and basal forebrain cholinergic neuron morphology during aging in the Ts65Dn mouse model of Down syndrome - Brian E. Powers; Ramon Velazquez; Christy M. Kelley; Jessica A. Ash; Myla S. Strawderman; Melissa J. Alldred; Stephen D. Ginsberg; Elliott J. Mufson; Barbara J. Strupp (Brain Structure and Function, 2016)

A keystone ecologist: Robert Treat Paine, 1933–2016 - James A. Estes; Paul K. Dayton; Peter Kareiva; Simon A. Levin; Jane Lubchenco; Bruce A. Menge; Stephen R. Palumbi; Mary E. Power; John Terborgh (Ecology, 2016)
Robert T. Paine, who passed away on 13 June 2016, is among the most influential people in the history of ecology. Paine was an experimentalist, a theoretician, a practitioner, and proponent of the “ecology of place,” and a deep believer in the importance of natural history to ecological understanding. His scientific legacy grew from the discovery of a link between top‐down forcing and species diversity, a breakthrough that led to the ideas of both keystone species and trophic cascades, and to our early understanding of the mosaic nature of biological communities, causes of zonation across physical gradients, and the intermediate‐disturbance hypothesis of species diversity. Paine's influence as a mentor was equally important to the growth of ecological thinking, natural resource conservation, and policy. He served ecology as an Ecological Society of America president, an editor of the Society's journals, a member of and contributor to the National Academy of Sciences and the National Research Council, and an in‐demand advisor to various state and federal agencies. Paine's broad interests, enthusiasm, charisma, and humor deeply affected our lives and the lives of so many others.

Burbot and large hydropower in North America: benefits, threats and research needs for mitigation - P. M. Harrison; L. F. G. Gutowsky; E. G. Martins; D. A. Patterson; S. J. Cooke; M. Power (Fisheries Management and Ecology, 2016)
In North America, burbot Lota lota (L.), interactions with hydropower are common, southern burbot populations are endangered and hydropower has been implicated in the decline. Thus, the objectives of this review were to identify threats and benefits of hydropower to riverine and reservoir dwelling burbot, assess overall impacts and identify key research needs for mitigation. Review findings suggest that while winter hydropower discharge regimes threaten riverine burbot spawning, burbot often successfully exploit reservoir environments. Further, while turbine entrainment has been hypothesised as a factor in the decline of burbot populations, low adult vulnerability to passage and a high resilience to juvenile removals likely mean risk to populations is low. Identified research needs include better definitions of flow and temperature requirements for riverine burbot and a quantification of the potential for reservoirs to act as source populations for downstream impacted zones. This review highlights the Pacific watershed focus of existing work and calls for status assessments and ecological research of burbot in North American Arctic and Atlantic watersheds where large hydropower and burbot interactions are common yet rarely studied.

Differences in corticospinal excitability to the biceps brachii between arm cycling and tonic contraction are not evident at the immediate onset of movement - Davis A. Forman; Devin T. G. Philpott; Duane C. Button; Kevin E. Power (Experimental Brain Research, 2016)

Using models to guide field experiments: a priori predictions for the CO 2 response of a nutrient‐ and water‐limited native Eucalypt woodland - Belinda E. Medlyn; Martin G. De Kauwe; Sönke Zaehle; Anthony P. Walker; Remko A. Duursma; Kristina Luus; Mikhail Mishurov; Bernard Pak; Benjamin Smith; Ying‐Ping Wang; Xiaojuan Yang; Kristine Y. Crous; et al. (Global Change Biology, 2016)
The response of terrestrial ecosystems to rising atmospheric CO 2 concentration (C a ), particularly under nutrient‐limited conditions, is a major uncertainty in Earth System models. The Eucalyptus Free‐Air CO 2 Enrichment (Euc FACE ) experiment, recently established in a nutrient‐ and water‐limited woodland presents a unique opportunity to address this uncertainty, but can best do so if key model uncertainties have been identified in advance. We applied seven vegetation models, which have previously been comprehensively assessed against earlier forest FACE experiments, to simulate a priori possible outcomes from Euc FACE . Our goals were to provide quantitative projections against which to evaluate data as they are collected, and to identify key measurements that should be made in the experiment to allow discrimination among alternative model assumptions in a postexperiment model intercomparison. Simulated responses of annual net primary productivity ( NPP ) to elevated C a ranged from 0.5 to 25% across models. The simulated reduction of NPP during a low‐rainfall year also varied widely, from 24 to 70%. Key processes where assumptions caused disagreement among models included nutrient limitations to growth; feedbacks to nutrient uptake; autotrophic respiration; and the impact of low soil moisture availability on plant processes. Knowledge of the causes of variation among models is now guiding data collection in the experiment, with the expectation that the experimental data can optimally inform future model improvements.

Temporal plasticity in thermal‐habitat selection of burbot Lota lota a diel‐migrating winter‐specialist - P. M. Harrison; L. F. G. Gutowsky; E. G. Martins; D. A. Patterson; S. J. Cooke; M. Power (Journal of Fish Biology, 2016)
In this study, animal‐borne telemetry with temperature sensors was coupled with extensive habitat temperature monitoring in a dimictic reservoir, to test the following hypotheses: behavioural thermoregulation occurs throughout the year and temperature selection varies on a diel and seasonal basis, in a winter‐specialist diel‐migrating fish. Burbot Lota lota demonstrated nightly behavioural thermoregulation throughout the year, with a large seasonal shift between selection for very cold temperatures ( L. lota avoided habitats warmer than optimal for reproduction and feeding during the spawning and non‐reproductive periods, respectively, active selection was limited to selection for 4–6° C habitat during the prespawning period. Although behavioural thermoregulation explained the night‐time migration, behavioural thermoregulation only partially explained daytime behaviour, indicating that diel migration is best explained by a combination of factors. Thus, thermal‐habitat selection was a good predictor of night‐time habitat occupancy in a diel‐migrating species. Together, these results show that thermal‐habitat selection by fishes may be important throughout the year and a more seasonally plastic behaviour than previously recognized.

A moving target—incorporating knowledge of the spatial ecology of fish into the assessment and management of freshwater fish populations - Steven J. Cooke; Eduardo G. Martins; Daniel P. Struthers; Lee F. G. Gutowsky; Michael Power; Susan E. Doka; John M. Dettmers; David A. Crook; Martyn C. Lucas; Christopher M. Holbrook; Charles C. Krueger (Environmental Monitoring and Assessment, 2016)

Examining rip current escape strategies in non-traditional beach morphologies - Ben R. Van Leeuwen; R. Jak McCarroll; Robert W. Brander; Ian L. Turner; Hannah E. Power; Anthony J. Bradstreet (Natural Hazards, 2016)

Slimy Sculpin (Cottus cognatus) annual growth in contrasting regulated and unregulated riverine environments - B. Kelly; K. E. Smokorowski; M. Power (Hydrobiologia, 2016)

Dry Matter Losses and Greenhouse Gas Emissions From Outside Storage of Short Rotation Coppice Willow Chip - Carly Whittaker; Nicola E. Yates; Stephen J. Powers; Tom Misselbrook; Ian Shield (BioEnergy Research, 2016)

An analysis of P seudomonas genomic diversity in take‐all infected wheat fields reveals the lasting impact of wheat cultivars on the soil microbiota - T. H. Mauchline; D. Chedom‐Fotso; G. Chandra; T. Samuels; N. Greenaway; A. Backhaus; V. McMillan; G. Canning; S. J. Powers; K. E. Hammond‐Kosack; P. R. Hirsch; I. M. Clark; et al. (Environmental Microbiology, 2015)
Summary Manipulation of the soil microbiota associated with crop plants has huge promise for the control of crop pathogens. However, to fully realize this potential we need a better understanding of the relationship between the soil environment and the genes and phenotypes that enable microbes to colonize plants and contribute to biocontrol. A recent 2 years of investigation into the effect of wheat variety on second year crop yield in the context of take‐all fungal infection presented the opportunity to examine soil microbiomes under closely defined field conditions. Amplicon sequencing of second year soil samples showed that P seudomonas spp. were particularly affected by the wheat cultivar grown in year one. Consequently, 318 rhizosphere‐associated P seudomonas fluorescens strains were isolated and characterized across a variety of genetic and phenotypic traits. Again, the wheat variety grown in the first year of the study was shown to exert considerable selective pressure on both the extent and nature of P seudomonas genomic diversity. Furthermore, multiple significant correlations were identified within the phenotypic/genetic structure of the Pseudomonas population, and between individual genotypes and the external wheat field environment. The approach outlined here has considerable future potential for our understanding of plant–microbe interactions, and for the broader analysis of complex microbial communities.

Mainstem‐tributary linkages by mayfly migration help sustain salmonids in a warming river network - Hiromi Uno; Mary E. Power (Ecology Letters, 2015)
Animal migrations can link ecosystems across space. We discovered an aquatic insect that migrates between a river mainstem and its tributaries, and provides an important trophic subsidy for tributary predators. A mayfly, Ephemerella maculata , rears in a warm, sunlit productive river mainstem, then migrates as adults to cool, shaded unproductive tributaries where they oviposit and die. This migration tripled insect flux into a tributary for 1 month in summer. A manipulative field experiment showed that this E. maculata subsidy nearly tripled the growth of the young of the year steelhead trout ( Oncorhynchus mykiss ) in the recipient tributary over the summer months, and was more important than terrestrial invertebrate subsidies, which have been considered the primary food source for predators in small, forested creeks. By delivering food subsidies from productive but warming river mainstems to cool but food‐limited tributaries, aquatic insect migrations could enhance resilience to cool‐water predators in warming river networks.

The community ecology of pathogens: coinfection, coexistence and community composition - Eric W. Seabloom; Elizabeth T. Borer; Kevin Gross; Amy E. Kendig; Christelle Lacroix; Charles E. Mitchell; Erin A. Mordecai; Alison G. Power (Ecology Letters, 2015)
Disease and community ecology share conceptual and theoretical lineages, and there has been a resurgence of interest in strengthening links between these fields. Building on recent syntheses focused on the effects of host community composition on single pathogen systems, we examine pathogen (microparasite) communities using a stochastic metacommunity model as a starting point to bridge community and disease ecology perspectives. Such models incorporate the effects of core community processes, such as ecological drift, selection and dispersal, but have not been extended to incorporate host–pathogen interactions, such as immunosuppression or synergistic mortality, that are central to disease ecology. We use a two‐pathogen susceptible‐infected ( SI ) model to fill these gaps in the metacommunity approach; however, SI models can be intractable for examining species‐diverse, spatially structured systems. By placing disease into a framework developed for community ecology, our synthesis highlights areas ripe for progress, including a theoretical framework that incorporates host dynamics, spatial structuring and evolutionary processes, as well as the data needed to test the predictions of such a model. Our synthesis points the way for this framework and demonstrates that a deeper understanding of pathogen community dynamics will emerge from approaches working at the interface of disease and community ecology.

Genetic diversity, population structure and phenotypic variation in European Salix viminalis L. (Salicaceae) - S. Berlin; S. O. Trybush; J. Fogelqvist; N. Gyllenstrand; H. R. Hallingbäck; I. Åhman; N-E. Nordh; I. Shield; S. J. Powers; M. Weih; U. Lagercrantz; A-C. Rönnberg-Wästljung; et al. (Tree Genetics & Genomes, 2014)

The potential for indirect effects between co‐flowering plants via shared pollinators depends on resource abundance, accessibility and relatedness - Luísa Gigante Carvalheiro; Jacobus Christiaan Biesmeijer; Gita Benadi; Jochen Fründ; Martina Stang; Ignasi Bartomeus; Christopher N. Kaiser‐Bunbury; Mathilde Baude; Sofia I. F. Gomes; Vincent Merckx; Katherine C. R. Baldock; Andrew T. D. Bennett; et al. (Ecology Letters, 2014)
Co‐flowering plant species commonly share flower visitors, and thus have the potential to influence each other's pollination. In this study we analysed 750 quantitative plant–pollinator networks from 28 studies representing diverse biomes worldwide. We show that the potential for one plant species to influence another indirectly via shared pollinators was greater for plants whose resources were more abundant (higher floral unit number and nectar sugar content) and more accessible. The potential indirect influence was also stronger between phylogenetically closer plant species and was independent of plant geographic origin (native vs. non‐native). The positive effect of nectar sugar content and phylogenetic proximity was much more accentuated for bees than for other groups. Consequently, the impact of these factors depends on the pollination mode of plants, e.g. bee or fly pollinated. Our findings may help predict which plant species have the greatest importance in the functioning of plant–pollination networks.

The Role of Nitrogen Deposition in Widespread Plant Community Change Across Semi-natural Habitats - Chris D. Field; Nancy B. Dise; Richard J. Payne; Andrea J. Britton; Bridget A. Emmett; Rachel C. Helliwell; Steve Hughes; Laurence Jones; Steven Lees; Jonathan R. Leake; Ian D. Leith; Gareth K. Phoenix; et al. (Ecosystems, 2014)

Multivariate analysis of MLH1 c.1664T>C (p.Leu555Pro) mismatch repair gene variant demonstrates its pathogenicity - M. P. Farrell; D. J. Hughes; M. Drost; A. J. Wallace; R. J. Cummins; T. A. Fletcher; M. A. Meany; E. W. Kay; N. de Wind; D. G. Power; E. J. Andrews; A. J. Green; et al. (Familial Cancer, 2013)

Head Impact Exposure in Youth Football: Elementary School Ages 9–12 Years and the Effect of Practice Structure - Bryan R. Cobb; Jillian E. Urban; Elizabeth M. Davenport; Steven Rowson; Stefan M. Duma; Joseph A. Maldjian; Christopher T. Whitlow; Alexander K. Powers; Joel D. Stitzel (Annals of Biomedical Engineering, 2013)

Head Impact Exposure in Youth Football: High School Ages 14 to 18 Years and Cumulative Impact Analysis - Jillian E. Urban; Elizabeth M. Davenport; Adam J. Golman; Joseph A. Maldjian; Christopher T. Whitlow; Alexander K. Powers; Joel D. Stitzel (Annals of Biomedical Engineering, 2013)

Food webs in Mediterranean rivers - Mary E. Power; Joseph R. Holomuzki; Rex L. Lowe (Hydrobiologia, 2013)

A Probabilistic Tsunami Hazard Study of the Auckland Region, Part II: Inundation Modelling and Hazard Assessment - E. M. Lane; P. A. Gillibrand; X. Wang; W. Power (Pure and Applied Geophysics, 2013)

Effects of an exercise and hypocaloric healthy eating program on biomarkers associated with long-term prognosis after early-stage breast cancer: a randomized controlled trial - E. Scott; A. J. Daley; H. Doll; N. Woodroofe; R. E. Coleman; N. Mutrie; H. Crank; H. J. Powers; J. M. Saxton (Cancer Causes & Control, 2013)

Molecular and cellular changes in skin and muscle during metamorphosis of Atlantic halibut (Hippoglossus hippoglossus) are accompanied by changes in deiodinases expression - M. A. Campinho; M. Galay-Burgos; N. Silva; R. A. Costa; R. N. Alves; G. E. Sweeney; D. M. Power (Cell and Tissue Research, 2012)

Long‐term nitrogen additions increase likelihood of climate stress and affect recovery from wildfire in a lowland heath - Georgina E. Southon; Emma R. Green; Alan G. Jones; Chris G. Barker; Sally A. Power (Global Change Biology, 2012)
Increases in the emissions and associated atmospheric deposition of nitrogen (N) have the potential to cause significant changes to the structure and function of N‐limited ecosystems. Here, we present the results of a long‐term (13 year) experiment assessing the impacts of N addition (30 kg ha −1 yr −1 ) on a UK lowland heathland under a wide range of environmental conditions, including the occurrence of prolonged natural drought episodes and a severe summer fire. Our findings indicate that elevated N deposition results in large, persistent effects on Calluna growth, phenology and chemistry, severe suppression of understorey lichen flora and changes in soil biogeochemistry. Growing season rainfall was found to be a strong driver of inter‐annual variation in Calluna growth and, although interactions between N and rainfall for shoot growth were not significant until the later phase of the experiment, N addition exacerbated the extent of drought injury to Calluna shoots following naturally occurring droughts in 2003 and 2009. Following a severe wildfire at the experimental site in 2006, heathland regeneration dynamics were significantly affected by N, with a greater abundance of pioneering moss species and suppression of the lichen flora in plots receiving N additions. Significant interactions between climate and N were also apparent post fire, with the characteristic stimulation in Calluna growth in +N plots suppressed during dry years. Carbon (C) and N budgets demonstrate large increases in both above‐ and below‐ground stocks of these elements in N‐treated plots prior to the fire, despite higher levels of soil microbial activity and organic matter turnover. Although much of the organic material was removed during the fire, pre‐existing treatment differences were still evident following the burn. Post fire accumulation of below‐ground C and N stocks was increased rapidly in N‐treated plots, highlighting the role of N deposition in ecosystem C sequestration.

Effects of Flow Regimes Altered by Dams on Survival, Population Declines, and Range‐Wide Losses of California River‐Breeding Frogs - SARAH J. KUPFERBERG; WENDY J. PALEN; AMY J. LIND; STEVE BOBZIEN; ALESSANDRO CATENAZZI; JOE DRENNAN; MARY E. POWER (Conservation Biology, 2012)
Widespread alteration of natural hydrologic patterns by large dams combined with peak demands for power and water delivery during summer months have resulted in frequent aseasonal flow pulses in rivers of western North America. Native species in these ecosystems have evolved with predictable annual flood‐drought cycles; thus, their likelihood of persistence may decrease in response to disruption of the seasonal synchrony between stable low‐flow conditions and reproduction. We evaluated whether altered flow regimes affected 2 native frogs in California and Oregon (U.S.A.) at 4 spatial and temporal extents. We examined changes in species distribution over approximately 50 years, current population density in 11 regulated and 16 unregulated rivers, temporal trends in abundance among populations occupying rivers with different hydrologic histories, and within‐year patterns of survival relative to seasonal hydrology. The foothill yellow‐legged frog (Rana boylii), which breeds only in flowing water, is more likely to be absent downstream of large dams than in free‐flowing rivers, and breeding populations are on average 5 times smaller in regulated rivers than in unregulated rivers. Time series data (range = 8 − 19 years) from 5 populations of yellow‐legged frogs and 2 populations of California red‐legged frogs (R. draytonii) across a gradient of natural to highly artificial timing and magnitude of flooding indicate that variability of flows in spring and summer is strongly correlated with high mortality of early life stages and subsequent decreases in densities of adult females. Flow management that better mimics natural flow timing is likely to promote persistence of these species and others with similar phenology.

Variable Responses of Lowland Tropical Forest Nutrient Status to Fertilization and Litter Manipulation - Emma J. Sayer; S. Joseph Wright; Edmund V. J. Tanner; Joseph B. Yavitt; Kyle E. Harms; Jennifer S. Powers; Michael Kaspari; Milton N. Garcia; Benjamin L. Turner (Ecosystems, 2012)

Modulation of voltage-gated sodium channels hyperpolarizes the voltage threshold for activation in spinal motoneurones - Kevin E. Power; Kevin P. Carlin; Brent Fedirchuk (Experimental Brain Research, 2012)

Non-cancer endpoints in BRCA1/2 carriers after risk-reducing salpingo-oophorectomy - J. V. Cohen; L. Chiel; L. Boghossian; M. Jones; J. E. Stopfer; J. Powers; T. R. Rebbeck; K. L. Nathanson; S. M. Domchek (Familial Cancer, 2012)

Red snapper management in the Gulf of Mexico: science- or faith-based? - J. H. Cowan; C. B. Grimes; W. F. Patterson; C. J. Walters; A. C. Jones; W. J. Lindberg; D. J. Sheehy; W. E. Pine; J. E. Powers; M. D. Campbell; K. C. Lindeman; S. L. Diamond; et al. (Reviews in Fish Biology and Fisheries, 2011)

Earth stewardship: a strategy for social–ecological transformation to reverse planetary degradation - F. Stuart Chapin; Steward T. A. Pickett; Mary E. Power; Robert B. Jackson; David M. Carter; Clifford Duke (Journal of Environmental Studies and Sciences, 2011)

Development of the Brain’s Functional Network Architecture - Alecia C. Vogel; Jonathan D. Power; Steven E. Petersen; Bradley L. Schlaggar (Neuropsychology Review, 2010)

Expression of the myosin light chains 1, 2 and 3 in the muscle of blackspot seabream (Pagellus bogaraveo, Brunnich), during development - P. Silva; D. M. Power; L. M. P. Valente; N. Silva; R. A. F. Monteiro; E. Rocha (Fish Physiology and Biochemistry, 2010)

Chemical characterization of oligosaccharides in the milk of six species of New and Old world monkeys - Kohta Goto; Kenji Fukuda; Akitsugu Senda; Tadao Saito; Kazumasa Kimura; Kenneth E. Glander; Katie Hinde; Wolfgang Dittus; Lauren A. Milligan; Michael L. Power; Olav T. Oftedal; Tadasu Urashima (Glycoconjugate Journal, 2010)

Local context drives infection of grasses by vector‐borne generalist viruses - Elizabeth T. Borer; Eric W. Seabloom; Charles E. Mitchell; Alison G. Power (Ecology Letters, 2010)
Ecology Letters (2010) 13: 810–818 Abstract Host characteristics commonly determine infection risk, but infection can also be mediated by regional‐ or local‐scale variation in the biotic and abiotic environment. Experiments can clarify the relative importance of these factors. We quantified drivers of infection by barley and cereal yellow dwarf viruses (B/CYDV), a group of generalist, vector‐borne grass pathogens, at hierarchically nested spatial scales (10 5 –1 m) by planting individuals of six common grass species into five Pacific Coast grassland sites spanning 7° of latitude (> 5000 total hosts) and applying a factorial combination of nitrogen and phosphorus fertilizer. Infection differed most among experimental blocks (10 2 –10 3 m scale), suggesting that local factors control infection risk; infection increased with cover of long‐lived hosts and phosphorus, but not nitrogen, fertilization. For B/CYDV, local context more strongly predicts infection risk than host species traits or regional context; such spatially nested experiments can clarify the factors underlying variation in infection risk.

Viral diversity and prevalence gradients in North American Pacific Coast grasslands - Eric W. Seabloom; Elizabeth T. Borer; Charles E. Mitchell; Alison G. Power (Ecology, 2010)
Host–pathogen interactions may be governed by the number of pathogens coexisting within an individual host (i.e., coinfection) and among different hosts, although most sampling in natural systems focuses on the prevalence of single pathogens and/or single hosts. We measured the prevalence of four barley and cereal yellow dwarf viruses (B/CYDVs) in three grass species at 26 natural grasslands along a 2000‐km latitudinal gradient in the western United States and Canada. B/CYDVs are aphid‐vectored RNA viruses that cause one of the most prevalent of all plant diseases worldwide. Pathogen prevalence and coinfection were uncorrelated, suggesting that different forces likely drive them. Coinfection, the number of viruses in a single infected host (α diversity), did not differ among host species but increased roughly twofold across our latitudinal transect. This increase in coinfection corresponded with a decline in among‐host pathogen turnover (β diversity), suggesting that B/CYDVs in northern populations experience less transmission limitation than in southern populations. In contrast to pathogen diversity, pathogen prevalence was a function of host identity as well as biotic and abiotic environmental conditions. Prevalence declined with precipitation and increased with soil nitrate concentration, an important limiting nutrient for hosts and vectors of B/CYDVs. This work demonstrates the need for further studies of processes governing coinfection, and the utility of applying theory developed to explain diversity in communities of free‐living organisms to pathogen systems.

Collaborative Problem Solving Using an Industrial Ecology Approach - Susan E. Boehme; Marta A. Panero; Gabriela R. Muñoz; Charles W. Powers; Sandra N. Valle (Journal of Industrial Ecology, 2009)
Summary Over the course of ten years, a consortium of stakeholders (the Harbor Consortium) used a collaborative approach to identify viable pollution prevention (P2) strategies for specific contaminants, namely mercury, cadmium, polychlorinated biphenyls (PCBs), dioxins, and polycyclic aromatic hydrocarbons (PAHs) as well as suspended solids entering the New York/New Jersey Harbor. The project, titled “The New York/New Jersey Harbor Watershed Pollution Prevention and Industrial Ecology Project,” in a very conscious and overt way engaged stakeholders in the process of developing P2 recommendations for the Harbor. The industrial ecology (IE) tools applied by the Harbor Consortium include substance flow analysis (SFA), material flow analysis (MFA), and, to a limited extent, life cycle analysis (LCA) and fate and transport analysis (F&T), to quantify and characterize how the contaminants flow through the regional economy and the Harbor Watershed once released to the environment. The application of these scientific tools to five contaminants at such a large geographical scale, within the context of a broad and inclusive stakeholder process, and with the goal of identifying and implementing pollution prevention strategies, led to a wide range of surprising outcomes and lessons learned. Undertaking this IE research with the key institutions and stakeholders at the table resulted in the identification and the implementation of many P2 opportunities.

Effects of Human Trampling on Populations of Soil Fauna in the McMurdo Dry Valleys, Antarctica - EDWARD AYRES; JOHNSON N. NKEM; DIANA H. WALL; BYRON J. ADAMS; J. E. BARRETT; EMMA J. BROOS; ANDREW N. PARSONS; LAURA E. POWERS; BREANA L. SIMMONS; ROSS A. VIRGINIA (Conservation Biology, 2008)
Antarctic ecosystems are often considered nearly pristine because levels of anthropogenic disturbance are extremely low there. Nevertheless, over recent decades there has been a rapid increase in the number of people, researchers and tourists, visiting Antarctica. We evaluated, over 10 years, the direct impact of foot traffic on the abundance of soil animals and soil properties in Taylor Valley within the McMurdo Dry Valleys region of Antarctica. We compared soils from minimally disturbed areas with soils from nearby paths that received intermediate and high levels of human foot traffic (i.e., up to approximately 80 passes per year). The nematodes Scottnema lindsayae and Eudorylaimus sp. were the most commonly found animal species, whereas rotifers and tardigrades were found only occasionally. On the highly trampled footpaths, abundance of S. lindsayae and Eudorylaimus sp. was up to 52 and 76% lower, respectively, than in untrampled areas. Moreover, reduction in S. lindsayae abundance was more pronounced after 10 years than 2 years and in the surface soil than in the deeper soil, presumably because of the longer period of disturbance and the greater level of physical disturbance experienced by the surface soil. The ratio of living to dead Eudorylaimus sp. also declined with increased trampling intensity, which is indicative of increased mortality or reduced fecundity. At one site there was evidence that high levels of trampling reduced soil CO 2 fluxes, which is related to total biological activity in the soil. Our results show that even low levels of human traffic can significantly affect soil biota in this ecosystem and may alter ecosystem processes, such as carbon cycling. Consequently, management and conservation plans for Antarctic soils should consider the high sensitivity of soil fauna to physical disturbance as human presence in this ecosystem increases.

Stoichiometry of soil enzyme activity at global scale - Robert L. Sinsabaugh; Christian L. Lauber; Michael N. Weintraub; Bony Ahmed; Steven D. Allison; Chelsea Crenshaw; Alexandra R. Contosta; Daniela Cusack; Serita Frey; Marcy E. Gallo; Tracy B. Gartner; Sarah E. Hobbie; et al. (Ecology Letters, 2008)
Extracellular enzymes are the proximate agents of organic matter decomposition and measures of these activities can be used as indicators of microbial nutrient demand. We conducted a global‐scale meta‐analysis of the seven‐most widely measured soil enzyme activities, using data from 40 ecosystems. The activities of β‐1,4‐glucosidase, cellobiohydrolase, β‐1,4‐ N ‐acetylglucosaminidase and phosphatase g −1 soil increased with organic matter concentration; leucine aminopeptidase, phenol oxidase and peroxidase activities showed no relationship. All activities were significantly related to soil pH. Specific activities, i.e. activity g −1 soil organic matter, also varied in relation to soil pH for all enzymes. Relationships with mean annual temperature (MAT) and precipitation (MAP) were generally weak. For hydrolases, ratios of specific C, N and P acquisition activities converged on 1 : 1 : 1 but across ecosystems, the ratio of C : P acquisition was inversely related to MAP and MAT while the ratio of C : N acquisition increased with MAP. Oxidative activities were more variable than hydrolytic activities and increased with soil pH. Our analyses indicate that the enzymatic potential for hydrolyzing the labile components of soil organic matter is tied to substrate availability, soil pH and the stoichiometry of microbial nutrient demand. The enzymatic potential for oxidizing the recalcitrant fractions of soil organic material, which is a proximate control on soil organic matter accumulation, is most strongly related to soil pH. These trends provide insight into the biogeochemical processes that create global patterns in ecological stoichiometry and organic matter storage.

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Over-expression of a gibberellin 2-oxidase gene from Phaseolus coccineus L. enhances gibberellin inactivation and induces dwarfism in Solanum species - C. Dijkstra; E. Adams; A. Bhattacharya; A. F. Page; P. Anthony; S. Kourmpetli; J. B. Power; K. C. Lowe; S. G. Thomas; P. Hedden; A. L. Phillips; M. R. Davey (Plant Cell Reports, 2008)

Nutrient loads to surface water from row crop production - Susan E. Powers (The International Journal of Life Cycle Assessment, 2007)

Nutrient loads to surface water from row crop production - Susan E. Powers (The International Journal of Life Cycle Assessment, 2007)

Pyrethrin and pyrethroid exposures in the United States: A longitudinal analysis of incidents reported to poison centers - Laura E. Power; Daniel L. Sudakin (Journal of Medical Toxicology, 2007)

Occurrence of Cryptosporidium parvum and Bacterial Pathogens in Faecal Material in the Red Fox (Vulpes vulpes) Population - Y. Nagano; M. B. Finn; C. J. Lowery; T. Murphy; J. Moriarty; E. Power; D. Toolan; A. O’Loughlin; M. Watabe; K. A. McCorry; E. Crothers; J. S. G. Dooley; et al. (Veterinary Research Communications, 2007)

Analysis of clonal germplasm from five Saccharum species: S. barberi, S. robustum, S. officinarum, S. sinense and S. spontaneum. A study of inter- and intra species relationships using microsatellite markers - J. Steven Brown; R. J. Schnell; E. J. Power; Stephanie L. Douglas; David N. Kuhn (Genetic Resources and Crop Evolution, 2007)

An assessment of de‐calcification procedures for δ 13 C and δ 15 N analysis of yellow perch, walleye and Atlantic salmon scales - R. N. Sinnatamby; J. E. Bowman; J. B. Dempson; M. Power (Journal of Fish Biology, 2007)
The scales of three species of fishes, yellow perch Perca flavescens , walleye Sander vitreus and Atlantic salmon Salmo salar , were acidified and the isotopic signatures were compared to non‐acidified scales from the same fishes. No significant acidification effects on either carbon or nitrogen isotope signatures were found. Results contrast with earlier literature findings noting significant acidification effects and suggest acidification tests be undertaken before scales are used for temporal reconstruction of fish food web positions.

Molecular, cellular and histological changes in skin from a larval to an adult phenotype during bony fish metamorphosis - Marco A. Campinho; Nádia Silva; Glen E. Sweeney; Deborah M. Power (Cell and Tissue Research, 2006)

Biotic interactions and plant invasions - Charles E. Mitchell; Anurag A. Agrawal; James D. Bever; Gregory S. Gilbert; Ruth A. Hufbauer; John N. Klironomos; John L. Maron; William F. Morris; Ingrid M. Parker; Alison G. Power; Eric W. Seabloom; Mark E. Torchin; et al. (Ecology Letters, 2006)
Introduced plant populations lose interactions with enemies, mutualists and competitors from their native ranges, and gain interactions with new species, under new abiotic conditions. From a biogeographical perspective, differences in the assemblage of interacting species, as well as in abiotic conditions, may explain the demographic success of the introduced plant populations relative to conspecifics in their native range. Within invaded communities, the new interactions and conditions experienced by the invader may influence both its demographic success and its effects on native biodiversity. Here, we examine indirect effects involving enemies, mutualists and competitors of introduced plants, and effects of abiotic conditions on biotic interactions. We then synthesize ideas building on Darwin's idea that the kinds of new interactions gained by an introduced population will depend on its relatedness to native populations. This yields a heuristic framework to explain how biotic interactions and abiotic conditions influence invader success. We conclude that species introductions generally alter plants’ interactions with enemies, mutualists and competitors, and that there is increasing evidence that these altered interactions jointly influence the success of introduced populations.

Atlantic bluefin tuna: population dynamics, ecology, fisheries and management - Jean‐Marc Fromentin; Joseph E Powers (Fish and Fisheries, 2005)
Both old and new information on the biology and ecology of Atlantic bluefin tuna have confronted scientists with research challenges: research needs to be connected to current stock‐assessment and management issues. We review recent studies on habitat, migrations and population structure, stressing the importance of electronic tagging results in the modification of our perception of bluefin tuna population dynamics and behaviour. Additionally, we question, from both scientific and management perspectives, the usefulness of the classical stock concept and suggest other approaches, such as Clark's contingent and metapopulation theories. Current biological information confirms that a substantial amount of uncertainty still exists in the understanding of reproduction and growth. In particular, we focus on intriguing issues such as the difference in age‐at‐maturity between West Atlantic and Mediterranean bluefin tuna. Our description of Atlantic bluefin tuna fisheries places today's fishing patterns within the two millennium history of exploitation of this species: we discuss trap fisheries that existed between the 17th and the early 20th centuries; Atlantic fisheries during the 1950s and 1960s; and the consequences of the recent development of the sushi–sashimi market. Finally, we evaluate stock status and management issues since the early 1970s. While important uncertainties remain, when the fisheries history is confronted with evidence from biological and stock‐assessment studies, results indicate that Atlantic bluefin tuna has been undergoing heavy overfishing for a decade. We conclude that the current exploitation of bluefin tuna has many biological and economic traits that have led several fish stocks to extreme depletion in the past.

Redescriptions of Aphanurus stossichii (Monticelli, 1891) and A. virgula Looss, 1907 (Digenea: Hemiuridae) - Aneta Kostadinova; David I. Gibson; Juan Antonio Balbuena; Anne Marie Power; Francisco E. Montero; Ali Aydogdu; Juan Antonio Raga (Systematic Parasitology, 2004)

From risk assessment to sediment management an international perspective - Sabine E. Apitz; Elizabeth A. Power (Journal of Soils and Sediments, 2002)

A basal aquatic-terrestrial trophic link in rivers: algal subsidies via shore-dwelling grasshoppers - Justin L. Bastow; John L. Sabo; Jacques C. Finlay; Mary E. Power (Oecologia, 2002)

STOIC: a study of coupled model climatology and variability in tropical ocean regions - Davey M.; Huddleston M.; Sperber K.; Braconnot P.; Bryan F.; Chen D.; Colman R.; Cooper C.; Cubasch U.; Delecluse P.; DeWitt D.; Fairhead L.; et al. (Climate Dynamics, 2002)

Molecular systematics of Solanum section Lycopersicum (Lycopersicon) using the nuclear ITS rDNA region - J. A. Marshall; S. Knapp; M. R. Davey; J. B. Power; E. C. Cocking; M. D. Bennett; A. V. Cox (Theoretical and Applied Genetics, 2001)

ENSIP: the El Niño simulation intercomparison project - M. Latif; K. Sperber; J. Arblaster; P. Braconnot; D. Chen; A. Colman; U. Cubasch; C. Cooper; P. Delecluse; D. Dewitt; L. Fairhead; G. Flato; et al. (Climate Dynamics, 2001)

A simple and rapid procedure to establish embryogenic cell suspensions as a source of protoplasts for efficient plant regeneration from two Chinese commercial rice cultivars - K. Tang; X. Sun; D. An; J. B. Power; E. C. Cocking; M. R. Davey (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

Nutrient induced changes in the species composition of epiphytes on Cladophora glomerata Kütz. (Chlorophyta) - Jane C. Marks; Mary E. Power (Hydrobiologia, 2001)

Lizard diversity and agricultural disturbance in a Caribbean forest landscape - Richard E. Glor; Alexander S. Flecker; Michael F. Benard; Alison G. Power (Biodiversity and Conservation, 2001)

The seasonal cycle in coupled ocean-atmosphere general circulation models - C. Covey; A. Abe-Ouchi; G. J. Boer; B. A. Boville; U. Cubasch; L. Fairhead; G. M. Flato; H. Gordon; E. Guilyardi; X. Jiang; T. C. Johns; H. Le Treut; et al. (Climate Dynamics, 2000)

Combined PI–DAPI staining (CPD) reveals NOR asymmetry and facilitates karyotyping of plant chromosomes - S. C. Andras; T. P. V. Hartman; J. Alexander; R. McBride; J. A. Marshall; J. B. Power; E. C. Cocking; M. R. Davey (Chromosome Research, 2000)

Central and peripheral tissue distribution of diclofenac after subcutaneous injection in the rat - R. F. Grace; S. R. Edwards; L. E. Mather; Y. Lin; I. Power (Inflammopharmacology, 2000)

Regression and Dimensional Analysis for Modeling Two‐Phase Flow - Jahangir Morshed; Susan E. Powers (Transport in Porous Media, 2000)

A Drop-spreading Technique to Produce Cytoplasm-free Mitotic Preparations from Plants with Small Chromosomes - S. C. Andras; T. P. V. Hartman; J. A. Marshall; R. Marchant; J. B. Power; E. C. Cocking; M. R. Davey (Chromosome Research, 1999)

Intergeneric somatic hybrids of rice [Oryza sativa L. (+) Porteresia coarctata (Roxb.) Tateoka] - N. B. Jelodar; N. W. Blackhall; T. P. V. Hartman; D. S. Brar; G. Khush; M. R. Davey; E. C. Cocking; J. B. Power (Theoretical and Applied Genetics, 1999)

Effects of water velocity on algal carbon isotope ratios: Implications for river food web studies - Jacques C. Finlay; Mary E. Power; Gilbert Cabana (Limnology and Oceanography, 1999)
We used variation in algal d 13 C between river habitats to study the spatial scale of energy flow through river food webs. We found a strong negative relationship between herbivore d 13 C (which reflects algal d 13 C) and water velocity in three productive Northern California rivers but not in unproductive streams. The contrast among habitats suggests that water velocity affects algal d 13 C most strongly when CO2 availability is low relative to photosynthetic rates. Our results help explain the wide variation in published river biota d 13 C and show that past studies using carbon isotope analyses may have significantly underestimated the importance of algal‐derived carbon to river food webs. While flow‐related variation in d 13 C complicates this common application of carbon isotope analysis, we show that it provides a natural tracer of the flux of algal production derived from different habitats within rivers to higher trophic levels. Measurements of consumer d 13 C showed that most invertebrate and vertebrate consumers relied on local production, except for filter‐feeding insects and steelhead trout, which relied on production derived from multiple sources. Stable carbon isotopes may thus be used to spatially delineate the habitats that support river food webs, providing previously unavailable information for understanding and managing river ecosystems.

Use of the Polymerase Chain Reaction for Rapid Detection of High-Level Mupirocin Resistance in Staphylococci - R. M. Anthony; A. M. Connor; E. G. M. Power; G. L. French (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Stress-inducible transgenic nematodes as biomonitors of soil and water pollution - R S Power; H E David; M H A Z Mutwakil; K Fletcher; C Daniells; M A Nowell; J L Dennis; A Martinelli; R Wiseman; E Wharf; D I de Pomerai (Journal of Biosciences, 1998)

A comparison of methods for direct gene transfer into maize (Zea mays L.) - E. M. Southgate; M. R. Davey; J. B. Power; R. J. Westcott (In Vitro Cellular & Developmental Biology - Plant, 1998)

Induction of heat shock protein 27 by hydroxyurea and its relationship to experimental metastasis - Allen E. Eskenazi; Jennifer Powers; Jan Pinkas; Steffi Oesterreich; Suzanne A. W. Fuqua; Christopher N. Frantz (Clinical & Experimental Metastasis, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Homoeologous pairing and recombination in backcross derivatives of tomato somatic hybrids [Lycopersicon esculentum (+) L. peruvianum] - A. S. Parokonny; J. A. Marshall; M. D. Bennett; E. C. Cocking; M. R. Davey; J. Brian Power (Theoretical and Applied Genetics, 1997)

Characterisation of an avian influenza virus nucleoprotein expressed inE. coli and in insect cells - V. R. Harley; K. A. Mather; B. E. Power; J. L. McKimm-Breschkin; P. J. Hudson (Archives of Virology, 1990)

Biochemical genetics of Fundulus heteroclitus (L.). IV. Spatial variation in gene frequencies of Idh-A, Idh-B, 6-Pgdh-A, and Est-S - Robert E. Cashon; Rebecca J. Van Beneden; Dennis A. Powers (Biochemical Genetics, 1981)

Biochemical genetics of Fundulus heteroclitus (L.). III. Inheritance of isocitrate dehydrogenase (Idh-A and Idh-B), 6-phosphogluconate dehydrogenase (6-Pgdh-A), and serum esterase (Est-S) polymorphisms - Rebecca J. Van Beneden; Robert E. Cashon; Dennis A. Powers (Biochemical Genetics, 1981)